Red-emitting phosphors having small particle sizes, methods of making same, and devices
By dissolving the Mn source in HF in the composite fluoride material and combining it with H2MF6 and A-source solutions, the problem of difficult doping of high manganese content under small particle size is solved, and efficient phosphor preparation is achieved, suitable for miniaturized LED backlight sources.
Patent Information
- Application Number
- CN202380042987.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-04
- Filing Date
- 2023-05-04
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to achieve doping of high manganese content under smaller particle sizes in composite fluoride materials, affecting the performance of red-emitting phosphors.
The Mn source is dissolved in HF, followed by addition of H2MF6 to form a metastable solution, which is subsequently combined with the solution from A source to form a Mn4+ doped composite fluoride phosphor.
Doping of high manganese content at small particle size is achieved, the quantum efficiency and color stability of the phosphor is improved, and it is suitable for the backlight of the new generation of miniaturized LEDs.
Smart Images

Figure CN119522261A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority to U.S. Provisional Patent Application Serial No. 63 / 338,428, filed on May 4, 2022, which is hereby incorporated by reference in its entirety. Background Art
[0003] The field of the invention relates generally to methods for preparing red-emitting phosphors having small particle sizes, and more particularly to methods for preparing complex fluoride phosphors having micron or submicron particle sizes and uniform particle size distribution.
[0004] Based on Mn 4+ Red-emitting phosphors of activated composite fluoride materials (such as those described in U.S. Pat. Nos. 7,358,542, 7,497,973, and 7,648,649) can be used in combination with yellow / green-emitting phosphors (such as YAG:Ce) to obtain warm white light (CCT<5000K on the blackbody locus, color rendering index (CRI)>80) from blue-emitting diodes (LEDs), i.e., light equivalent to that produced by current fluorescent, incandescent, and halogen lamps. These materials absorb blue light strongly and emit efficiently in the range between about 610nm and 658nm, with almost no deep red / NIR emission. The luminous efficiency of these materials is maximized compared to red phosphors with significant emission in darker reds with poor visual sensitivity. The quantum efficiency can exceed 85% under near ultraviolet (UV) or blue light (440nm-460nm) excitation. In addition, the use of red phosphors for displays can produce high color gamut and efficiency.
[0005] The industry trend is and continues to be toward devices that require smaller sized particles. New generation devices use smaller LEDs, such as mini LEDs and micro LEDs. Mini LEDs have a size of about 100 μm to 0.7 mm, while micro LEDs have a size of less than 100 μm. Displays can include miniaturized backlights arranged with individual mini LEDs or micro LEDs, self-luminous phosphor-converted (PC) mini LEDs or micro LEDs, films, and printed inks for preparing the films and LEDs.
[0006] The new generation of devices requires low energy consumption, compact size, high brightness and large color gamut coverage. 4+ Red emitting phosphors of activated complex fluoride materials are desirable materials due to their high color gamut and quantum efficiency. Smaller particle sizes are required in new generation devices and high manganese content is desired.
[0007] For the preparation of Mn with improved color stability 4+Methods of doping complex fluoride phosphors are described in US Pat. Nos. 8,906,724 and 11,193,059 and other patents and patent applications assigned to General Electric Company or Current. Summary of the invention
[0008] In one aspect, there is provided a method for preparing a Mn 4+ Methods of doping phosphors
[0009] A x [MF y ]:Mn 4+ I.
[0010] The method comprises combining a first aqueous solution comprising a source of Mn with a second solution comprising H2MF6 to form a third solution, and combining the third solution with a fourth solution comprising a source of A to form Mn 4+ Doped phosphors, wherein A is Li, Na, K, Rb, Cs, or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd, or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0011] In another aspect, a method for preparing Mn of formula I is provided. 4+ Methods of doping phosphors.
[0012] A x [MF y ]:Mn 4+ I.
[0013] The method comprises combining an aqueous solution comprising a Mn source and A2SiF6 with an anti-solvent solution comprising an anti-solvent to form a Mn 4+ Doped phosphors, wherein A is H, Li, Na, K, Rb, Cs, or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd, or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0014] In another aspect, a method for preparing Na2SiF6:Mn 4+ The method comprises combining (i) an aqueous solution comprising a Mn source and H2SiF6 with (ii) a solution comprising a Na source to form Na2SiF6:Mn 4+ Phosphor.
[0015] In one aspect, there is provided a Mn of Formula I 4+ Doped phosphor.
[0016] A x [MF y ]:Mn 4+ I.
[0017] The phosphor has a D50 particle size of less than 5 μm and has a Mn content of at least 1.5 wt %, wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0018] In another aspect, there is provided a Mn of Formula I 4+ Doped phosphor.
[0019] A x [MF y ]:Mn 4+ I.
[0020] The phosphor has an organic phosphate surface coating and a D50 particle size of less than 5 μm, wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0021] In one aspect, a device is provided that includes an LED light source optically coupled and / or radiatively connected to a phosphor composition. The phosphor composition includes Mn of Formula I 4+ Doped phosphor
[0022] A x [MF y ]:Mn 4+ I.
[0023] The phosphor has a D50 particle size of less than 5 μm and has a Mn content of at least 2.0 wt %, wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0024] In one aspect, a device is provided that includes an LED light source optically coupled and / or radiatively connected to a phosphor composition. The phosphor composition includes Mn of Formula I 4+ Doped phosphor
[0025] A x [MF y ]:Mn 4+ I.
[0026] The phosphor has a D50 particle size of less than 5 μm and an organic phosphate surface coating, wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a graph of the dissolution space of K2MnF6 (PFM) in a mixture of HF and H2SiF6 from an automated study, where the x-axis is the mole fraction of PFM and the y-axis is the volume ratio of 49% HF to 35% H2SiF6.
[0028] Figure 2 is a schematic diagram of a microfluidic device according to an exemplary embodiment.
[0029] Figure 3A is a schematic cross-sectional view of a device according to one embodiment of the present disclosure.
[0030] Figure 3B is a schematic cross-sectional view of a device according to an exemplary embodiment of the present disclosure.
[0031] Figure 3C is a schematic cross-sectional view of a device according to an exemplary embodiment of the present disclosure.
[0032] Figure 3D is a schematic cross-sectional view of a device according to an exemplary embodiment of the present disclosure.
[0033] Figure 3E is a schematic cross-sectional view of a device according to an exemplary embodiment of the present disclosure.
[0034] Figure 4 is a schematic cross-sectional view of a lighting device according to an embodiment of the present disclosure.
[0035] Figure 5 is a schematic cross-sectional view of a lighting device according to another embodiment of the present disclosure.
[0036] Figure 6 is a cross-sectional side perspective view of a lighting device according to one embodiment of the present disclosure.
[0037] Fig. 7A is a schematic perspective view of a surface mount device (SMD) according to one embodiment of the present disclosure.
[0038] Figure 7B is a schematic cross-sectional view of a SMD according to an exemplary embodiment of the present disclosure.
[0039] Figure 7C is a schematic cross-sectional view of a SMD according to an exemplary embodiment of the present disclosure.
[0040] Figure 8 is a scanning electron micrograph (SEM) of sample GRC092421ATGA (614) in Example 1.
[0041] Fig. 9 is a contour plot of D50 particle size in μm showing the mixture space where CTAB is fixed at 2 parts and the band of minimum particle size is located at about 9 parts of 3,7-dimethyl-3-octanol as described in Example 1.
[0042] Fig.10 is a contour plot of %QE showing the mixture space where CTAB is fixed at 2 parts and the region of high %QE is found to be at low 3,7-dimethyl-3-octanol amounts and a ratio of heptane to hydrofluoric acid of about 55:30 (v / v) as described in Example 1.
[0043] Fig.11 is a graph showing the correlation of Average Particle Size (micrometers) on the y-axis to % CTAB on the x-axis, as described in Example 1.
[0044] Fig. 12A This is the particle size distribution of sample E112421AMgGA(632) in Example 1.
[0045] Fig. 12B is a scanning electron micrograph (SEM) of sample E112421AMgGA(632) in Example 1.
[0046] Fig.13 is a graph showing the correlation of %Mn on the y-axis to %CTAB on the x-axis for a mixture formulation as described in Example 1.
[0047] Fig.14 is a graph showing % QE (y-axis) versus D50 particle size (x-axis) as described in Example 1.
[0048] Fig.15is the SEM of sample 1 in Example 2.
[0049] Fig.16 This is the SEM of sample 2 in Example 2.
[0050] Fig.17 This is the SEM of sample 3 in Example 2.
[0051] Fig.18 is the SEM of the synthesized sample in Example 8.
[0052] Fig.19 is the reflection IR spectrum of the PFS powder in Example 8.
[0053] Fig. 20 is the SEM of the synthetic sample of Example 9.
[0054] Fig.21 is the volume of Proglyme (antisolvent) used in the synthesis (ml) on the x-axis versus PFS:Mn on the y-axis 4+ Plot of particle size D50 (μm).
[0055] Fig. 22 is PFS:Mn on the x-axis 4+ Plot of particle size D50 (μm) versus quantum efficiency (QE, %) on the y-axis. DETAILED DESCRIPTION
[0056] In the following description and claims, reference will be made to a number of terms which will be defined to have the following meanings.
[0057] The singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise.
[0058] Approximate language as used herein throughout the specification and claims can be used to modify any quantitative representation that allows variation without causing a change in the basic function associated therewith. Therefore, values modified by one or more terms such as "about", "substantially" and "approximately" are not limited to the exact values specified. At least in some cases, approximate language can correspond to the accuracy of the instrument used to measure the value. In this article and throughout the specification and claims, range limitations can be combined and / or interchanged, unless otherwise indicated by context or language, such ranges are determined and include all subranges contained therein. All references are incorporated herein by reference.
[0059] The square brackets in the formula indicate that at least one of the elements within the brackets is present in the phosphor material, and any combination of two or more thereof may be present, as limited by the stoichiometry of the composition. For example, the formula [Ca, Sr, Ba] 3MgSi2O8:Eu2+ ,Mn 2+ Contains at least one of Ca, Sr or Ba or any combination of two or more of Ca, Sr or Ba. Examples include Ca3MgSi2O8:Eu 2+ ,Mn 2+ ;Sr3MgSi2O8:Eu 2+ ,Mn 2+ or Ba3MgSi2O 8 :Eu 2+ ,Mn 2+ A formula with an activator after a colon ":" indicates that the phosphor composition is doped with the activator. A formula showing more than one activator separated by "," after a colon ":" indicates that the phosphor composition is doped with any one activator or two activators. For example, the formula [Ca, Sr, Ba] 3MgSi2O8:Eu 2+ ,Mn 2+ Covering [Ca,Sr,Ba]3MgSi2O8:Eu 2+ 、Formula [Ca, Sr, Ba] 3MgSi2O8: Mn 2+ Or [Ca, Sr, Ba] 3MgSi2O8:Eu 2+ and Mn 2+ .
[0060] Based on Mn 4+ Red-emitting phosphors of activated composite fluoride materials require smaller particle sizes for use in next generation devices. It is also desirable to incorporate higher levels of manganese into composite fluoride materials to improve blue or near UV absorption. However, the inventors have found that for composite fluoride materials, incorporation of higher levels of manganese into phosphor compounds cannot be achieved at smaller particle sizes.
[0061] U.S. Patent No. 11,193,059 describes a method for preparing Mn of Formula I having a small particle size. 4+ Methods of doping phosphors
[0062] A x [MF y ]:Mn 4+ I
[0063] The U.S. patent is incorporated herein by reference. A first solution comprising a source of A is combined with a second solution comprising HF and H2MF6 in the presence of a source of Mn to form a 4+ A doped phosphor wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is the absolute value of the charge of the [MFy] ion; and y is 5, 6 or 7.
[0064] The inventors have found that a Mn source such as potassium hexafluoromanganate K2MnF6 (PFM) dissolves slowly and has limited solubility in the second solution containing HF and H2MF6. The inventors have also found that when the solubility limit of the Mn source is approached, the Mn 4+ When the phosphor is doped, the QE measurement decreases even when the Mn source appears to be completely dissolved. Figure 1 , where the Mn source is PFM and H2MF6 is hexafluorosilicic acid (H2SiF6). The x-axis is the mole fraction of PFM and the y-axis is the volume ratio of 49% HF to 35% H2SiF6.
[0065] The inventors have found that by dissolving the Mn source in HF before adding H2MF6, a homogeneous solution can be obtained. For example, the solubility of PFM in 49% HF is about 75 mg / mL, which is significantly higher than the solubility in HF / H2SiF6 solution (about 52 mg / mL). The subsequent addition of H2SiF6 produces a metastable solution, and when a solution containing a source of A (which can be KF) is added, there is rapid coprecipitation, resulting in high quality phosphors with higher manganese dopant concentrations and smaller sizes than previously achievable.
[0066] In one aspect, there is provided a method for preparing a Mn 4+ Methods of doping phosphors
[0067] A x [MF y ]:Mn 4+ I.
[0068] The method comprises combining a first aqueous solution comprising a source of Mn with a second solution comprising H2MF6 to form a third solution, and combining the third solution with a fourth solution comprising a source of A to form Mn 4+ Doped phosphors, wherein A is Li, Na, K, Rb, Cs, or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd, or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0069] Mn of Formula I 4+ Doped phosphors are complex fluoride materials or coordination compounds containing at least one coordination center surrounded by fluoride ions acting as ligands and, if necessary, charge compensated by counter ions. 4+ In the example, the coordination center is Si and the counter ion is K. The activator ion (Mn4+ ) also acts as a coordination center, replacing a portion of the host lattice center, such as Si. The host lattice (including the counterions) can further modify the excitation and emission characteristics of the activator ion.
[0070] In certain embodiments, the coordination center of the phosphor (i.e., M in Formula I) is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd, or a combination thereof. More particularly, the coordination center can be Si, Ge, Ti, or a combination thereof. The counter ion or A in Formula I can be Li, Na, K, Rb, Cs, or a combination thereof, more particularly K or Na. Examples of phosphors of Formula I include K2[SiF6]:Mn 4+ 、K2[TiF6]:Mn 4+ 、K2[SnF6]:Mn 4+ 、Cs2[TiF6]:Mn 4+ 、Rb2[TiF6]Mn 4 + 、Cs2[SiF6]:Mn 4+ 、Rb2[SiF6]:Mn 4+ 、Na2[SiF6]:Mn 4+ 、Na2[TiF6]:Mn 4+ 、Na2[ZrF6]:Mn 4+ 、K3[ZrF7]:Mn 4+ 、K3[BiF6]K3[YF6]:Mn 4+ 、K3[LaF6]:Mn 4+ 、K3[GdF6]:Mn 4+ 、K3[NbF7]:Mn 4+ 、K3[TaF7]:Mn 4+ In a specific embodiment, the phosphor of formula I is K2SiF6:Mn 4+ (PFS) or Na2[SiF6]:Mn 4+ (NSF).
[0071] The first aqueous solution comprises a Mn source dissolved in a solvent such as aqueous HF. Suitable materials for use as a Mn source include, for example, K2MnF6, Na2MnF6, KMnO4, K2MnCl6, MnF4, MnF3, MnF2, MnO2, and combinations thereof, particularly potassium hexafluoromanganate (K2MnF6) or sodium hexafluoromanganate (Na2MnF6). The concentration of the compound or compounds used as a Mn source is not critical and is generally limited by its solubility in the solution.
[0072] In one embodiment, the first aqueous solution comprises HF. The HF concentration in the first solution may be at least 15 wt %, particularly at least 25 wt %, more particularly at least 30 wt %. The aqueous HF may be any concentration, such as 20% HF in water, 49% HF in water, or 55% HF in water.
[0073] The second solution comprises H2MF6 and may further comprise a solvent such as aqueous HF. M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof. H2MF6 may be a compound containing Si having good solubility in the second solution, such as hexafluorosilicic acid (H2SiF6). The compound H2SiF6 is advantageous because it has a very high solubility in water and it does not contain alkali metal elements as impurities. The source of M may be a single compound or a combination of two or more compounds.
[0074] In one embodiment, the second solution comprises HF. The HF concentration in the second solution can be at least 15% by weight, particularly at least 25% by weight, more particularly at least 30% by weight. Aqueous HF can be any concentration, such as 20% HF in water, 49% HF in water, or 55% HF in water. Water can also be added to the second solution to reduce the concentration of HF to reduce particle size and increase product yield. The concentration of the material used as the source of M can be ≤25% by weight, particularly ≤15% by weight. In one embodiment, the volume ratio of 35% H2SiF6 to 49% HF in the second solution is at least 1:2.5. In particular, the ratio is at least 1:2.2.
[0075] The method includes combining a first aqueous solution containing a Mn source with a second solution containing H2MF6 to form a third solution. A uniform solution can be obtained by dissolving the Mn source in an aqueous solvent in the first solution and then adding the M source in the second solution. Combining the first solution and the second solution produces a uniform metastable third solution.
[0076] The fourth solution comprises a source of A. A is Li, Na, K, Rb, Cs or a combination thereof. The source of A can be a single compound or a mixture of two or more compounds. Suitable materials include, but are not limited to, KF, KHF2, KC6H7O7 (potassium citrate), KOH, KCl, KBr, KI, KHSO4, KOCH3, K2S2O8, K2CO3, sodium acetate, NaF, NaCF3CO2, NaClO4, Na6(PO3)6, NaSO4 or a combination thereof, particularly KF, KHF2, potassium citrate, and more particularly KF. In another embodiment, A is Na, and the fourth solution comprises a source of Na, such as NaF. Changing the ionic strength of different compounds of the source of A can be a product Mn 4+ Doped phosphors offer a wider range of particle sizes.
[0077] The concentration of A source in the fourth solution can be at least 6M, particularly at least 7.8M. The fourth solution can include a solvent. In other embodiments, the solvent can be HF, water, an alkane (such as heptane), a non-solvent or anti-solvent for phosphor products, or a combination of solvents can be used. Suitable non-solvent or anti-solvent materials include di(propylene glycol) dimethyl ether (proglyme), acetone, acetic acid, isopropanol, ethanol, methanol, acetonitrile, dimethylformamide and combinations thereof.
[0078] The solvent concentration in the fourth solution may be at least 15 wt %, particularly at least 25 wt %, more particularly at least 30 wt %. In one embodiment, the solvent is aqueous HF, which may be any concentration, such as 20% HF in water, 49% HF in water, or 55% HF in water.
[0079] In one embodiment, the source of A is particles, and these particles may be coated with an acid-degradable polymer such as ethylcellulose. The coating degrades in an acidic solvent and allows for a controlled and uniform release of A in the combined solution of the third and fourth solutions, which results in Mn having very small size and uniform size distribution. 4+ In one embodiment, the source of A is K + In another embodiment, the source of A is KF, and the KF crystals are coated with an acid-degradable polymer. When the polymer coating degrades in an acidic solvent such as HF, the presence of K + controlled release of and controlled precipitation of the product phosphor particles.
[0080] The fourth solution can be a microemulsion and can include a surfactant and a cosurfactant. Suitable surfactants include nonionic surfactants, anionic surfactants and cationic surfactants, including but not limited to aliphatic amines such as hexadecyltrimethylammonium bromide (CTAB), fluorocarbon surfactants, carboxylates such as stearic acid and stearate or oleic acid and oleate, organic phosphates such as bis (2-ethylhexyl) phosphate and organic sulfates. Suitable nonionic surfactants include Polyoxyethylene sorbitan fatty acid esters commercially available under the trade name fluorocarbon surfactants such as NOVEC TM ammonium fluoroalkyl sulfonamides, and polyoxyethylene nonylphenol ethers. Additional examples of suitable surfactants are described in US 2015 / 0329770; U.S. Patent No. 7,985,723; and Kikuyarna et al., IEEE Transactions on Semiconductor Manufacturing, Vol. 3, No. 3, August 1990, pp. 99-108.
[0081] The co-surfactant may include a surfactant from the above list, an alcohol or a C4-C 10 Amine. In one embodiment, the co-surfactant may be a tertiary alcohol, such as 3,7-dimethyl-3-octanol. In another embodiment, the fourth solution is a microemulsion and comprises heptane, CTAB, and 3,7-dimethyl-3-octanol.
[0082] The third solution is combined with the fourth solution to form Mn of Formula I 4+ When the third solution and the fourth solution are combined, rapid nucleation occurs and Mn 4+ Particles of the doped phosphor rapidly precipitate from the combined solution. After the product liquid is discharged from the reactor, the Mn can be separated from the product liquid by simply decanting the solvent or by filtration. 4+ The doped phosphors may be post-processed as described below and as described in US Pat. Nos. 8,252,613, 8,710,487 or US Pat. No. 9,399,732.
[0083] The first solution and the second solution are combined to form a third solution. In one embodiment, the third solution is mixed and fed into the fourth solution. In one embodiment, the third solution is mixed and quickly fed into the fourth solution, or combined with the fourth solution. In one embodiment, the third solution is mixed for about 1s to about 10min, and then combined with the fourth solution. In another embodiment, the third solution is mixed for about 1s to about 5min, and then combined with the fourth solution. In another embodiment, the third solution is mixed for about 1s to about 3min, and then combined with the fourth solution. In another embodiment, the third solution is mixed for about 1s to about 1min, and then combined with the fourth solution. In another embodiment, the third solution is mixed for about 1s to about 30s, and then combined with the fourth solution. In another embodiment, the third solution is mixed for about 1s to about 10s, and then combined with the fourth solution. In one embodiment, the third solution is mixed for about 30s to about 3min, and then combined with the fourth solution. In another embodiment, the third solution is mixed for about 1min to about 3min, and then combined with the fourth solution. In another embodiment, the third solution is mixed for about 10s to about 10s, and then combined with the fourth solution. In one embodiment, the third solution is mixed for about 30s to about 3min, and then combined with the fourth solution. In another embodiment, the third solution is mixed for about 1min to about 3min, and then combined with the fourth solution.
[0084] A peristaltic pump may be used to combine the solutions. In one embodiment, two separate peristaltic pumps are used to combine the first solution and the second solution into a third solution, and the third solution is fed or injected into the fourth solution.
[0085] The amount of raw materials used generally corresponds to the amount of each component in the desired composition, except that there may be an excess of source A. The flow rates can be adjusted so that the H2MF6 source and the Mn source are added in approximately stoichiometric ratios, while the source A exceeds the stoichiometric amount. In many embodiments, the source A is added in an amount ranging from about 150% to 300% molar excess, particularly about 175% to 300% molar excess. For example, in the case of Mn 4+ In doped K2SiF6, each mole of Mn 4+ K required for doped K2SiF6 + The stoichiometric amount is 2 moles, and the amount of KF or KHF2 used can be in the range of about 3.5 moles to about 6 moles of the product phosphor.
[0086] The molar ratio of A to M may be at least 5 / 1, and in particular embodiments may be at least 7 / 1, or at least 8 / 1, or at least 9 / 1. That is, the ratio of the total number of moles of the source of A in the fourth solution to the total number of moles of H2MF6 in the second solution may be at least 5 / 1, and in particular embodiments may be at least 7 / 1, 7 / 1, or at least 8 / 1, or at least 9 / 1.
[0087] For the preparation of Mn of Formula I 4+ The synthesis process of the doped phosphors can be a batch process or a continuous process.
[0088] In some embodiments, Mn of Formula I 4+ The synthesis of the doped phosphor can be carried out at low temperature to reduce the solubility of the product polymer in the reaction solution from the combined third solution and fourth solution. 4+ The solubility of the doped phosphor is reduced and the product polymer will precipitate out of the solution with a smaller particle size. In one embodiment, the reaction solution is at ice bath temperature or ice water bath temperature. In one embodiment, the ice bath temperature is from about 13°C to about -196°C. In another embodiment, the ice bath temperature is from about 0°C to about -20°C. In another embodiment, one or more of the first solution, the second solution, the third solution, and the fourth solution are at ice bath temperature or ice water bath temperature. In another embodiment, all solutions are at ice bath or ice water bath temperature.
[0089] In one embodiment, a NSF phosphor (Na2SiF6) with a small particle size and a high manganese content is prepared. In the first aqueous solution, the Mn source is K2MnF6 or Na2MnF6. In one embodiment, the first aqueous solution comprises HF at a concentration of 49% water or 20% water. In the second solution, H2MF6 is H2SiF6. The fourth solution includes a Na source and a solvent, such as distilled water or HF. In one embodiment, the A source is sodium acetate, NaF. NaCF3CO2, NaClO4, Na6(PO3)6 or NaSO4. The third solution and the fourth solution are reacted at an ice bath temperature or an ice water bath temperature. In one embodiment, the ice bath temperature is from about 13°C to about -196°C. In another embodiment, the ice bath temperature is from about 0°C to about -20°C. NSF phosphors exhibit fast decay times and can be used in inks or films for LEDs and on LEDs including small-sized LEDs. Changing the Na source and the Na molar ratio can adjust the particle size and promote Mn incorporation. Changing the ionic strength of different compounds of the Na source provides a wider range of particle sizes. Increasing the molar ratio of the Na source will increase the amount of Mn incorporated into the phosphor and the particle size of the phosphor particles. The NSF phosphor can be adjusted to a smaller particle size range while maintaining a good Mn incorporation rate.
[0090] The solution may additionally comprise one or more chelating agents, such as ammonium citrate, potassium citrate, iminodiacetic acid (IDA), and EDTA. In some embodiments, potassium citrate may be the A source.
[0091] In another embodiment, one or more of these solutions may further comprise an effective amount of a ligand to aid in the synthesis of small particle size Mn of Formula I by regulating the growth of the phosphor particles formed when the third solution and the fourth solution are combined. 4+The ligand contains a functional group that bonds to a polar particle such as a product phosphor particle. The ligand attaches to the phosphor particle and prevents the phosphor particle from further growing during the reaction. Suitable ligands are those that form nano-sized micelles in water but do not reduce the Mn during the synthesis reaction. 4+ An amphiphilic polymer with a valence state of . Examples of ligands include, but are not limited to, poly(styrene)-block-poly(acrylic acid), poly(ethylene oxide)-block-polycaprolactone, and poly(dimethylsiloxane)-block-methoxypolyethylene glycol. The ligand is dissolved in a polar solvent and dissolved in HF during the reaction of the phosphor particles. The phosphor particles are micron-sized or submicron-sized. In one embodiment, the phosphor particles have a D90 particle size of less than 3 μm and are suitable for ink preparation. The phosphor particles can be washed or rinsed to remove any undissolved ligands and can be post-processed as described herein.
[0092] One or more of these solutions may additionally contain one or more surfactants. Suitable surfactants for use in the methods herein include nonionic surfactants, anionic surfactants, and cationic surfactants, including but not limited to aliphatic amines such as hexadecyltrimethylammonium bromide (CTAB), fluorocarbon surfactants, carboxylates such as stearic acid and stearate or oleic acid and oleate, organic phosphates such as bis(2-ethylhexyl)phosphate, and organic sulfates. Suitable nonionic surfactants include Polyoxyethylene sorbitan fatty acid esters commercially available under the trade name fluorocarbon surfactants such as NOVEC TM Ammonium fluoroalkyl sulfonamides, and polyoxyethylene nonylphenol ethers. Additional examples of suitable surfactants are described in US 2015 / 0329770; U.S. Patent No. 7,985,723; and Kikuyarna et al., IEEE Transactions on Semiconductor Manufacturing, Vol. 3, No. 3, August 1990, pp. 99-108.
[0093] In other embodiments, one or more of these solutions may additionally contain one or more surfactants. The co-surfactant may include a surfactant from the above list, an alcohol, or a C4-C 10 Amines. In another embodiment, the co-surfactant may be a tertiary alcohol, such as 3,7-dimethyl-3-octanol. 3,7-dimethyl-3-octanol is a natural product containing a long alkyl chain and a tertiary alcohol.
[0094] In one embodiment, CTAB can be used in combination with 3,7-dimethyl-3-octanol. Both CTAB and 3,7-dimethyl-3-octanol are acidic and oxidatively stable in a solution containing HF and a source of Mn. In one embodiment, the ratio (v / w) of 3,7-dimethyl-3-octanol to CTAB is from about 0:1 to about 100:1, more particularly, from about 1:1 to about 20:1, even more particularly, from about 1:1 to about 10:1. In another embodiment, the ratio is from about 1:1 to about 5:1.
[0095] In some embodiments, the solution can be a microemulsion. The microemulsion consists of an organic phase and an aqueous phase, wherein at least one surfactant serves as an emulsifier. The organic phase may contain one or more organic solvents; suitable solvents include, but are not limited to, octanol, hexadecane, octadecane, octadecene, phenyldodecane, phenyltetradecane, or phenylhexadecane. The aqueous phase comprises one or more of the above-mentioned A source, M source, and Mn source and an aqueous solvent, such as aqueous HF or H2SiF6.
[0096] The microemulsion may additionally comprise one or more cosurfactants and / or one or more chelating agents. The ratio of the solution components may be adjusted so that they are above the critical micelle concentration. The microemulsion may be a reverse microemulsion consisting of reverse micelles containing an aqueous solvent and an A source, an M source and a Mn source dispersed in an organic solvent.
[0097] In one embodiment, the microemulsion of any solution comprises a surfactant, a co-surfactant, and a solvent.
[0098] In one embodiment, multiple microemulsions can be prepared. In another embodiment, solution 3 and solution 4 are microemulsions. In another embodiment, solution 2, solution 3, and solution 4 are microemulsions. In another embodiment, a single microemulsion is prepared. In another embodiment, solution 4 can be an emulsion.
[0099] In one embodiment, Mn 4+ The doped phosphor particles can be coated with a moisture resistant surfactant coating. The moisture resistant coating protects the Mn 4+ The doped phosphor is protected from water and oxidative degradation. In one embodiment, the coating comprises an organic material having a carboxylate group at one end and a hydrophobic group at the other end. The carboxylate group will bond to a large ionic size ion with a high coordination number, such as Ca 2+ or K + If the phosphor has no ions such as Ca on the surface 2+ or K +, the phosphor is first coated with CaF2 to form an outer shell layer. The phosphor is then treated with an organic material such as oleic acid to bind to the carboxylate groups of the organic material at the surface of the phosphor. The hydrophobic end groups of the organic material face the outside of the phosphor particles, which forms a moisture-proof coating on the phosphor particles.
[0100] In another embodiment, a microfluidic device can be used to sequentially react a source of Mn, H2MF6, and a source of A (all as described above) to form a Mn of Formula I as described above. 4+ Small size particles of doped phosphor. The particle size and uniform size distribution of the product phosphor is controlled in part by the small micron-sized channels of the microfluidic device. The channels in the microfluidic device have a diameter of about 1 micron to about 1000 microns. Figure 2 A microfluidic device 100 is shown. A first solution comprising a Mn source such as K2MnF6 and an aqueous HF solvent is continuously fed along a horizontal single-phase flow channel at 110. At 120, a second solution comprising H2MF6 such as H2SiF6 and an optional solvent is continuously added to the device in a reaction phase channel. At 130, the first solution and the second solution contact and mix to form a third solution, which continues to travel along the horizontal single-phase flow channel to the next reaction phase intersection at 150. At 140, a fourth solution comprising an A source such as KF and an optional solvent is continuously added to the device in the reaction phase channel. At 150, the fourth solution contacts and mixes with the third solution. When the third solution and the fourth solution contact and mix at the reaction phase intersection 150, rapid nucleation occurs and small-sized Mn 4+ Doped phosphor particles. The formed particles continue to travel along the horizontal channel at 160, exit the microfluidic device (not shown) and are collected. In some embodiments, microwave radiation can be applied at 150 to assist the nucleation step. The phosphor particles are micron-sized particles or nano-sized particles with uniform size distribution. The first solution, the second solution, the third solution, the fourth solution and the solvent are as described above. The product phosphor particles can be post-processed as described herein.
[0101] In one embodiment, a NSF phosphor (Na2SiF6) having a small particle size and a high manganese content is prepared. In one aspect, a method for preparing Na2SiF6:Mn 4+ The method comprises combining (i) a solution comprising a Mn source, H2SiF6 and HF with (ii) a solution comprising a Na source to form Na2SiF6:Mn 4+Phosphor, wherein the Mn source is K2MnF6 or Na2MnF6. HF can be aqueous HF with a concentration of 49% water or 20% water. The solution containing the Na source can also contain a solvent, such as distilled water or HF. Na sources include, but are not limited to, sodium acetate, NaF. NaCF3CO2, NaClO4, Na6(PO3)6 or NaSO4. These solutions are combined and reacted at an ice bath temperature or an ice water bath temperature. In one embodiment, the ice bath temperature is about 13°C to about -196°C. In another embodiment, the ice bath temperature is about 0°C to about -20°C. NSF phosphors exhibit fast decay times and can be used in inks or films for LEDs and on LEDs including small-sized LEDs. Changing the Na source and the Na molar ratio can adjust the particle size and promote Mn incorporation. Changing the ionic strength of different compounds of the Na source provides a wider range of particle sizes. Increasing the molar ratio of the Na source will increase the amount of Mn incorporated into the phosphor and the particle size of the phosphor particles. The NSF polymer can be tuned to a smaller particle size range while maintaining good Mn incorporation. The NSF phosphor can be post-processed as described herein.
[0102] The amount of raw materials used to prepare NSF generally corresponds to the amount of each component in the desired composition, except that there may be an excess of Na source. The flow rate can be adjusted so that the H2SiF6 source and the Mn source are added in a roughly stoichiometric ratio, while the Na source exceeds the stoichiometric amount. In many embodiments, the Na source is added in an amount ranging from about 150% to 300% molar excess, particularly about 175% to 300% molar excess. The molar ratio of the Na source to H2SiF6 can be at least 5 / 1, and in a specific embodiment can be at least 7 / 1, or at least 8 / 1, or at least 9 / 1. That is, the ratio of the total number of moles of the Na source to the total number of moles of H2SiF6 can be at least 5 / 1, and in a specific embodiment can be at least 7 / 1, 7 / 1, or at least 8 / 1, or at least 9 / 1.
[0103] The synthetic method for preparing NSF can be a batch method or a continuous method. These solutions can additionally contain one or more chelating agents, as described above. One or both of these solutions can additionally contain one or more surfactants, as described above. In other embodiments, one or both of these solutions can additionally contain one or more co-surfactants, as described above.
[0104] In some embodiments, one or both of these solutions can be microemulsions. Microemulsions are composed of an organic phase and an aqueous phase, wherein at least one surfactant is used as an emulsifier. The organic phase may include one or more organic solvents, as described above. The aqueous phase includes one or more of a Na source or a Mn source and an aqueous solvent, such as aqueous HF or H2SiF6. The microemulsion may additionally include one or more cosurfactants and / or one or more chelating agents. The ratio of the solution components may be adjusted so that they are above the critical micelle concentration. The microemulsion may be an inverse microemulsion composed of reverse micelles containing an aqueous solvent and Na sources, Mn sources, and Si sources dispersed in an organic solvent. In one embodiment, the solution comprising a Na source is a microemulsion comprising a surfactant, a cosurfactant, and a solvent.
[0105] In the preparation of Mn of Formula I as described herein 4+ After the doped phosphor, the product particles can be separated and further processed. In one embodiment, the phosphor can be annealed to improve stability, as described in U.S. Patent No. 8,906,724. In such embodiments, the product phosphor is maintained at an elevated temperature while in contact with an atmosphere containing a fluorine-containing oxidant. The fluorine-containing oxidant can be F2, HF, SF6, BrF5, NH4HF2, NH4F, KF, AlF3, SbF5, ClF3, BrF3, KrF2, XeF2, XeF4, XeF6, NF3, SiF4, PbF2, ZnF2, SnF2, CdF2 CdF2, C1-C4 fluorocarbons or combinations thereof. Examples of suitable fluorocarbons include CF4, C2F6, C3F8, CHF3, CF3CH2F and CF2CHF. In a particular embodiment, the fluorine-containing oxidant is F2. The amount of oxidant in the atmosphere can be varied to obtain a color stable phosphor, particularly in combination with variations in time and temperature. In the case where the fluorine-containing oxidant is F2, the atmosphere may contain at least 0.5% F2, but lower concentrations may also be effective in some embodiments. In particular, the atmosphere may contain at least 5% F2, and more particularly at least 20% F2. The atmosphere may additionally contain nitrogen, helium, neon, argon, krypton, xenon in any combination with the fluorine-containing oxidant. In a particular embodiment, the atmosphere consists of about 20% F2 and about 80% nitrogen.
[0106] The temperature at which the phosphor is contacted with the fluorine-containing oxidant is from about 200°C to about 700°C, particularly from about 350°C to about 600°C. During contact and in some embodiments, any temperature in the range of about 500°C to about 600°C. The phosphor is contacted with the oxidant for a period of time sufficient to convert the phosphor into a color-stable phosphor. Time and temperature are interrelated and can be adjusted together, for example, extending the time while lowering the temperature, or increasing the temperature while shortening the time. In a particular embodiment, the time is at least one hour, particularly at least four hours, more particularly at least six hours, and most particularly at least eight hours. After maintaining the desired period of time at an elevated temperature, the temperature in the furnace can be reduced at a controlled rate while maintaining an oxidizing atmosphere during the initial cooling period. Under controlled cooling. The temperature can be reduced to about 200°C. If necessary, control can be interrupted.
[0107] The manner in which the phosphor is contacted with the fluorine-containing oxidant is not critical and may be accomplished in any manner sufficient to convert the phosphor into a color-stable phosphor having the desired properties. In some embodiments, the chamber containing the phosphor may be dosed and then sealed so that an overpressure is created when the chamber is heated, and in other embodiments, a fluorine and nitrogen mixture is flowed throughout the annealing process to ensure a more uniform pressure. In some embodiments, additional doses of the fluorine-containing oxidant may be introduced after a period of time.
[0108] The annealed phosphor can be further treated with a saturated or near-saturated solution of the composition of formula II in aqueous hydrofluoric acid. This treatment improves the quantum efficiency and stability of the phosphor.
[0109] A x [MF y ] (II)
[0110] wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0111] The compound of formula II comprises at least MF for the host compound of the product phosphor y anion, and may also contain A of the compound of formula I + cation.
[0112] The near-saturated solution contains about 1%-5% excess aqueous HF added to the saturated solution. The concentration of HF in the solution is in the range of about 25% (weight / volume) to about 70% (weight / volume), particularly about 40% (weight / volume) to about 50% (weight / volume). Solutions with lower concentrations may result in reduced performance of the phosphor.
[0113] The amount of the treatment solution is in the range of about 2 ml / g product to 30 ml / g product, particularly about 5 ml / g product to 20 ml / g product, more particularly about 5 ml / g product to 15 ml / g product. The treated annealed phosphor can be isolated by filtration, washed with a solvent such as acetic acid and acetone to remove contaminants and traces of water, and stored under nitrogen.
[0114] For the product phosphor of formula K2SiF6:Mn, suitable materials for the compound of formula II include H2SiF6, Na2SiF6, (NH4)2SiF6, Rb2SiF6, Cs2SiF6 or a combination thereof, particularly H2SiF6, K2SiF6 and a combination thereof, more particularly K2SiF6. The treatment solution is a saturated solution or a nearly saturated solution of the compound of formula II in hydrofluoric acid. The nearly saturated solution contains about 1%-5% excess aqueous HF added to the saturated solution. The concentration of HF in the solution is in the range of about 25% (weight / volume) to about 70% (weight / volume), particularly about 40% (weight / volume) to about 50% (weight / volume). Solutions with lower concentrations may result in reduced performance of the phosphor. The amount of the treatment solution used is in the range of about 2ml / g product-30ml / g product, particularly about 5ml / g product-20ml / g product, more particularly about 5ml / g product-15ml / g product.
[0115] After treatment, the phosphor can be contacted with a fluorine-containing oxidant in gaseous form at a second, lower temperature. The second temperature can be the same as the first temperature, or can be lower than the first temperature, ranging up to and including 225°C, particularly up to and including 100°C, more particularly up to and including 90°C. The time of contact with the oxidant can be at least one hour, particularly at least four hours, more particularly at least six hours, and most particularly at least eight hours. In a particular embodiment, the phosphor is contacted with the oxidant at a temperature of about 90°C for a period of at least eight hours. The oxidant can be the same or different from the oxidant used in the first annealing step. In a particular embodiment, the fluorine-containing oxidant is F2. More particularly, the atmosphere can contain at least 20% F2. The phosphor can be contained in a container having a non-metallic surface to reduce metal contamination of the phosphor.
[0116] The treated phosphor can be vacuum filtered and washed with one or more solvents to remove HF and unreacted raw materials. Suitable materials for washing solvents include acetic acid and acetone and combinations thereof.
[0117] The treated phosphor may be coated with a manganese-free outer shell comprising a metal fluoride. The metal fluoride may be one or more of: calcium fluoride, strontium fluoride, magnesium fluoride, yttrium fluoride, scandium fluoride, and lanthanum fluoride. In a specific embodiment, the phosphor of formula I is K2[SiF6]:Mn 4+ And in one embodiment, the metal fluoride can be MgF2. The core-shell Mn of Formula I 4 + Doped phosphors and methods for their preparation are described in WO 2018 / 093832.
[0118] In another aspect, a method for preparing Mn of formula I is provided. 4+ Methods of doping phosphors.
[0119] A x [MF y ]:Mn 4+ I.
[0120] The method comprises combining an aqueous solution comprising a Mn source and A2SiF6 with an anti-solvent solution comprising an anti-solvent to form a Mn 4+ Doped phosphors, wherein A is H, Li, Na, K, Rb, Cs, or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd, or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0121] Suitable materials for the Mn source include, for example, K2MnF6, Na2MnF6, KMnO4, K2MnCl6, MnF4, MnF3, MnF2, MnO2, and combinations thereof, particularly potassium hexafluoromanganate (K2MnF6) or sodium hexafluoromanganate (Na2MnF6). The concentration of the compound or compounds used as the Mn source is not critical and is generally limited by its solubility in the solution.
[0122] In one embodiment, the aqueous solution is prepared by dissolving a Mn source in a 55% HF solution in water and adding a treatment solution comprising A2SiF6 in a 49% HF solution in water. In one embodiment, A2SiF6 is K2SiF6 or H2SiF6.
[0123] The HF concentration in the aqueous solution may be at least 15 wt%, particularly at least 25 wt%, more particularly at least 30 wt%. The aqueous HF may be any concentration, such as 20% HF in water, 49% HF in water, or 55% HF in water.
[0124] The antisolvent solution comprises an organic antisolvent. The organic antisolvent can be di(propylene glycol) dimethyl ether (proglyme), isopropanol, ethanol or acetone. In other embodiments, the antisolvent solution can comprise a surfactant. Examples of surfactants include organic sulfates, carboxylates such as oleic acid or stearic acid, or organic phosphates such as bis(2-ethylhexyl) phosphate. The antisolvent solution can also comprise a potassium source such as KF, hydrofluoric acid and / or water.
[0125] The antisolvent synthesis produced Mn of Formula I with small particle size. 4+ In some embodiments, the synthesized phosphor particles include a surface coating, which provides a phosphor with enhanced dispersibility and stability for inks and coatings. In one example, the manganese source is K2MnF6, the antisolvent solution includes an organic phosphate, and Mn 4+ The doped phosphor product is a PFS with an organophosphate coating having small sized particles, such as micron sized particles, submicron sized particles, or nano sized particles.
[0126] Mn of Formula I 4+ The doped phosphor has good quantum efficiency, high Mn 4+ content and very small particle sizes from micron to submicron. Mn of product formula I 4+ Doped phosphors can be used in inks, films, and small LEDs, such as mini-LEDs or micro-LEDs.
[0127] Mn of Formula I 4+ The doped phosphor has a very small particle size, which can be micron-sized particles to submicron-sized particles. In one embodiment, Mn 4+Doped phosphor particles can be nano-sized. The particle size of the phosphor powder can be conveniently measured by laser diffraction or optical microscopy, and commercially available software can generate particle size distribution and span. In one embodiment, the D50 particle size is less than 20 μm, less than 10 μm, particularly less than 5 μm, more particularly nano-sized. In one embodiment, the D50 particle size can be about 1 micron to about 20 microns. In another embodiment, the D50 particle size is about 1 micron to about 15 microns. In another embodiment, the D50 particle size is about 1 micron to about 10 microns. In another embodiment, the D50 particle size is about 1 micron to about 5 microns. In another embodiment, the D50 particle size is about 1 micron to about 3 microns. In another embodiment, the D50 particle size is about 50nm to about 1000nm. In another embodiment, the D50 particle size is about 100nm to about 1000nm. In another embodiment, the D50 particle size is about 200nm to about 1000nm. In another embodiment, the D50 particle size is from about 250nm to about 1000nm. In another embodiment, the D50 particle size is from about 500nm to about 1000nm. In another embodiment, the D50 particle size is from about 750nm to about 1000nm. In another embodiment, the D50 particle size is from about 50nm to about 10 microns. In another embodiment, the D50 particle size is from about 200nm to about 5 microns. In another embodiment, the D50 particle size is from about 250nm to about 5 microns. In another embodiment, the D50 particle size is from about 500nm to about 5 microns. In another embodiment, the D50 particle size is from about 750nm to about 5 microns. In another embodiment, the D50 particle size is from about 750nm to about 3 microns.
[0128] The span of the particle size distribution is not necessarily limited and can be less than 1.1. In another embodiment, the span of the particle size distribution is ≤ ± 1.0. The span is a measure of the width of the particle size distribution curve of the granular material or powder and is defined according to the following equation:
[0129]
[0130] Where D 50 is the median particle size in the volume distribution; D 90 is the particle size in a volume distribution that is larger than 90% of the particles in the distribution; and D 10 It is the particle size of particles larger than 10% of the volume distribution.
[0131] The particles have an aspect ratio of less than or equal to 3 / 1. The aspect ratio is the ratio of the largest dimension of the particle to the smallest dimension orthogonal thereto. The aspect ratio of the phosphor particles can vary from less than or equal to 3 / 1 to close to 1 for particles having a cubic or dodecahedral form.
[0132] Quantum efficiency (QE) measurements are known in the art and can be performed, for example, using a spectrometer. 4+ The doped phosphor has a high QE of at least 85%. In another embodiment, the QE exceeds 90%. In another embodiment, the QE exceeds 100%. In one embodiment, the QE is about 101% to 106%.
[0133] The amount of activator Mn incorporated into the red-emitting phosphor (referred to as Mn%) improves color conversion. Increasing the amount of Mn% incorporation improves color conversion by increasing the intensity of red light emission, maximizing the absorption of exciting blue light and reducing the amount of unconverted blue light or the penetration of blue light from blue LEDs.
[0134] In one embodiment, Mn of Formula I 4+ The doped phosphor has a Mn loading or Mn% of at least 1 wt %. In another embodiment, the phosphor has a Mn loading of at least 1.5 wt %. In another embodiment, the phosphor has a Mn loading of at least 2 wt %. In another embodiment, the phosphor has a Mn loading of at least 3 wt %. In another embodiment, the Mn% is greater than 3.0 wt %. In another embodiment, the content of Mn in the phosphor is about 1 wt % to about 4 wt %. In another embodiment, the content of Mn in the phosphor is about 2 wt % to about 4 wt %.
[0135] In one aspect, there is provided a Mn of Formula I 4+ Doped phosphor.
[0136] A x [MF y ]:Mn 4+ I.
[0137] The phosphor has an organic phosphate surface coating and a D50 particle size of less than 5 μm, wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0138] In another embodiment, the phosphor has a D50 particle size of less than 3 microns and a Mn content of at least 2.0 wt%. In another embodiment, the phosphor has a D50 particle size of less than 5 microns, a Mn content of at least 1.5 wt%, and a QE greater than 92%. In another embodiment, the phosphor has a D50 particle size of less than 3 microns, a Mn content of at least 2.0 wt%, and a QE greater than 100%.
[0139] In one aspect, a device is provided that includes an LED light source optically coupled and / or radiatively connected to a phosphor composition. The phosphor composition includes Mn of Formula I 4+ Doped phosphor
[0140] A x [MF y ]:Mn 4+ I.
[0141] The phosphor has a D50 particle size of less than 5 μm and has a Mn content of at least 2.0 wt %, wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0142] In another aspect, a device is provided that includes an LED light source optically coupled and / or radiatively connected to a phosphor composition. The phosphor composition includes Mn of Formula I 4+ Doped phosphor
[0143] A x [MF y ]:Mn 4+ I.
[0144] The phosphor has a D50 particle size of less than 5 μm and an organic phosphate surface coating, wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0145] The phosphor composition may include one or more other luminescent materials. Additional luminescent materials, such as blue, yellow, red, orange or other colored phosphors, may be used in the phosphor composition to tailor the white color of the resulting light and to produce a specific spectral power distribution.
[0146] Phosphors suitable for use in the phosphor composition include, but are not limited to: ((Sr 1-z [Ca,Ba,Mg,Zn] z ) 1-(x+w) [Li,Na,K,Rb] w Ce x )3(Al 1-y Si y ) 4+y+3(x-w) F1-y-3(x-w) , 0 < x ≤ 0.10, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, 0 ≤ w ≤ x; [Ca,Ce]3Sc2Si3O 12 (CaSiG); [Sr,Ca,Ba]3Al 1-x Si x O 4+x F 1-x :Ce 3+ (SASOF)); [Ba,Sr,Ca]5(PO4)3[Cl,F,Br,OH]:Eu 2+ ,Mn 2+ ; [Ba,Sr,Ca]BPO5:Eu 2+ ,Mn 2+ ; [Sr,Ca] 10 (PO4)6*vB2O3:Eu 2+ (where 0 < v ≤ 1); Sr2Si3O8*2SrCl2:Eu 2+ ; [Ca,Sr,Ba]3MgSi2O8:Eu 2+ ,Mn 2+ ; BaAl8O 13 :Eu 2+ ; 2SrO*0.84P2O5*0.16B2O3:Eu 2+ ; [Ba,Sr,Ca]MgAl 10 O 17 :Eu 2+ ,Mn 2+ ; [Ba,Sr,Ca]Al2O4:Eu 2+ ; [Y,Gd,Lu,Sc,La]BO3:Ce 3+ ,Tb 3+ ; ZnS:Cu + ,Cl - ; ZnS:Cu + ,Al 3+ ; ZnS:Ag + ,Cl - ; ZnS:Ag + ,Al 3+ ; [Ba,Sr,Ca]2Si 1-n O 4-2n :Eu 2+ (where 0 ≤ n ≤ 0.2); [Ba,Sr,Ca]2[Mg,Zn]Si2O7:Eu 2+ ; [Sr,Ca,Ba][Al,Ga,In]2S4:Eu 2+ ; [Y,Gd,Tb,La,Sm,Pr,Lu]3[Al,Ga] 5-a O 12-3 / 2a:Ce 3+ (where 0 ≤ a ≤ 0.5); [Ca,Sr]8[Mg,Zn](SiO4)4Cl2:Eu 2+ ,Mn 2+ ; Na2Gd2B2O7:Ce 3+ ,Tb 3+ ; [Sr,Ca,Ba,Mg,Zn]2P2O7:Eu 2+ ,Mn 2+ ; [Gd,Y,Lu,La]2O3:Eu 3+ ,Bi 3+ ; [Gd,Y,Lu,La]2O2S:Eu 3+ ,Bi 3+ ; [Gd,Y,Lu,La]VO4:Eu 3+ ,Bi 3+ ; [Ca,Sr,Mg]S:Eu 2+ ,Ce 3+ ; SrY2S4:Eu 2+ ; CaLa2S4:Ce 3+ ; [Ba,Sr,Ca]MgP2O7:Eu 2+ ,Mn 2+ ; [Y,Lu]2WO6:Eu 3+ ,Mo 6+ ; [Ba,Sr,Ca] b Si g N m :Eu 2+ (where 2b + 4g = 3m); Ca3(SiO4)Cl2:Eu 2+ ; [Lu,Sc,Y,Tb] 2-u-v Ce v Ca 1+ u Li w Mg 2-w P w [Si,Ge] 3-w O 12-u / 2 (where 0.5 ≤ u ≤ 1, 0 < v ≤ 0.1 and 0 ≤ w ≤ 0.2); [Y,Lu,Gd] 2-m [Y,Lu,Gd]Ca m Si4N 6+m C 1-m :Ce 3+ , (where 0 ≤ m ≤ 0.5); doped with Eu 2+ and / or Ce 3+ of [Lu,Ca,Li,Mg,Y], α - SiAlON; Sr(LiAl3N4):Eu 2+,[Ca,Sr,Ba]SiO2N2:Eu 2+ ,Ce 3+ ;β-SiAlON:Eu 2+ ;3.5MgO*0.5MgF2*GeO2:Mn 4+ ;Ca 1-c-f Ce c Eu f Al 1+c Si 1-c N 3, (where 0≤c≤0.2, 0≤f≤0.2); Ca 1-h-r Ce h Eu r Al 1-h (Mg, Zn) h S N 3, (where 0≤h≤0.2, 0≤r≤0.2); Ca 1-2s-t Ce s [Li,Na] s Eu t AlSiN 3, (where 0≤s≤0.2, 0≤t≤0.2, s+t>0); [Sr,Ca]AlSiN3 and Eu 2+ ,Ce 3+ ,Li2CaSiO4:Eu 2+ .
[0147] In a particular embodiment, the additional phosphor includes: [Y, Gd, Lu, Tb]3[Al, Ga]5O 12 :Ce 3+ 、β-SiAlON:Eu 2+ 、[Sr,Ca,Ba][Ga,Al]2S4:Eu 2+ 、[Li,Ca]α-SiAlON:Eu 2+ 、[Ba,Sr,Ca]2Si5N8:Eu 2+ 、[Ca,Sr]AlSiN3:Eu 2+ 、[Ba,Sr,Ca]LiAl3N4:Eu 2+ 、[Sr,Ca,Mg]S:Eu 2+ and [Ba,Sr,Ca]2Si2O4:Eu 2+ .
[0148] The phosphor composition may include at least one green-emitting phosphor. The green-emitting phosphor may include any suitable green-emitting phosphor, including uranium phosphors. In one embodiment, the green-emitting uranium phosphor includes, but is not limited to, Ba3(PO4)2(UO2)2P2O7, Ba3(PO4)2(UO2)2V2O7, γγ-Ba2UO2(PO4)2, BaMgUO2(PO4)2, BaZnUO2(PO4)2, Na2UO2P2O7, K2UO2P2O7, Rb2UO2P2O7, Cs2UO2P2O7, K4UO2(PO4) 2、 K4UO2(VO4)2 or NaUO2P3O9, as described in U.S. Patent No. 11,254,864, and incorporated herein.
[0149] Other additional luminescent materials suitable for use in the phosphor composition may include electroluminescent polymers such as polyfluorenes, preferably poly(9,9-dioctylfluorene) and copolymers thereof, such as poly(9,9′-dioctylfluorene-co-bis-N,N′-(4-butylphenyl)diphenylamine) (F8-TFB); poly(vinylcarbazole); polyphenylene vinylene; and derivatives thereof. In addition, the light-emitting layer may contain a blue, yellow, orange, green or red phosphorescent dye or metal complex, quantum dot material, or a combination thereof. Materials suitable for use as phosphorescent dyes include, but are not limited to, tris(1-phenylisoquinoline)iridium(III) (red dye), tris(2-phenylpyridine)iridium(green dye), and bis(2-(4,6-difluorophenyl)pyridine-N,C2)iridium(III) (blue dye). Fluorescent metal complexes and phosphorescent metal complexes commercially available from ADS (American Dyes Source, Inc.) may also be used. ADS green dyes include ADS060GE, ADS061GE, ADS063GE, ADS066GE, ADS078GE, and ADS090GE. ADS blue dyes include ADS064BE, ADS065BE, and ADS070BE. ADS red dyes include ADS067RE, ADS068RE, ADS069RE, ADS075RE, ADS076RE, ADS067RE, and ADS077RE.
[0150] Exemplary QD materials include, but are not limited to: Group II-IV compound semiconductors such as CdS, CdSe, CdS / ZnS, CdSe / ZnS, or CdSe / CdS / ZnS; Group II-VI such as CdTe, ZnSe, ZnTe, ZnS, HgTe, HgS, HgSe, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgS Te, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe; Group III-V or Group IV-VI compound semiconductors, Such as GaN, GaP, GaNP, GaNAs, GaPAs, GaAs, GaAlNP, GaAlNAs, GaAlPAs, GaInNP, GaInNAs, GaInPAs, AlN, AlNP, AlNAs, AlP, AlPAs, AlAs, InN, InNP, InP, InNAs, InPAs, InAS, InAlNP, InAlNAs, InAlPAs, PbS / ZnS or PbSe / ZnS; Group IV, such as Si, Ge, SiC and SiGe; chalcopyrite-type compounds, including but not limited to CuInS2, CuInSe2, CuGaS2, CuGaSe2, AgInS2, AgInSe2, AgGaS2, AgGaSe2; or perovskite QDs having the formula ABX3, wherein A is cesium, methylammonium or formamidine, B is lead or tin, and C is chloride, bromide or iodide. The quantum dot material may include a core-shell nanostructure having an Ag-In-Ga-S (AIGS) core and an Ag-Ga-S (AGS) shell.
[0151] In one embodiment, the perovskite quantum dot can be CsPbX3, wherein X is Cl, Br, I or a combination thereof. The average size of the QD material can be in the range of about 2nm to about 20nm. The surface of the QD particles can be further modified with ligands such as amine ligands, phosphine ligands, phospholipids and polyvinyl pyridine. In one aspect, the red phosphor can be a quantum dot material.
[0152] All semiconductor quantum dots may also have an appropriate shell or coating for passivation and / or environmental protection. The QD material may be a core / shell QD comprising a core, at least one shell coated on the core, and an outer coating comprising one or more ligands (preferably organic polymer ligands). Exemplary materials for preparing core-shell QDs include, but are not limited to, Si, Ge, Sn, Se, Te, B, C (including diamond), P, Co, Au, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdS e, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, MnS, MnSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, [Al, Ga, In]2[S, Se, Te]3, and suitable combinations of two or more such materials. Exemplary core-shell luminescent nanocrystals include, but are not limited to, CdSe / ZnS, CdSe / CdS, CdSe / CdS / ZnS, CdSeZn / CdS / ZnS, CdSeZn / ZnS, InP / ZnS, PbSe / PbS, PbSe / PbS, CdTe / CdS, and CdTe / ZnS.
[0153] In one embodiment, the phosphor composition may include scattering particles. In one embodiment, the scattering particles have a particle size of at least 1 μm. In another embodiment, the scattering particles have a particle size of about 1 μm to about 10 μm. In another embodiment, the scattering particles may include titanium dioxide, aluminum oxide (Al2O3), zirconium oxide, indium tin oxide, cerium oxide, tantalum oxide, zinc oxide, magnesium fluoride (MgF2), calcium fluoride (CaF2), strontium fluoride (SrF2), barium fluoride (BaF2), silver fluoride (AgF), aluminum fluoride (AlF3), or a combination thereof.
[0154] The ratio of each individual phosphor to other luminescent materials in the phosphor composition can be varied depending on the characteristics of the desired light output. The relative proportions of the individual phosphors to other luminescent materials in various phosphor compositions can be adjusted so that when their emissions are blended and used in a device (e.g., a lighting device), visible light of predetermined x and y values is produced on the CIE chromaticity diagram.
[0155] The phosphor composition may be in the form of an ink composition or a paste composition, which may be applied to a substrate such as an LED light source or formed into a film. The ink composition may be blended with a binder or a solvent.
[0156] Examples of binders include, but are not limited to, silicone polymers, polysiloxanes, ethyl cellulose, polystyrene, polyacrylates, polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polycarbonate, polyurethane, polyetheretherketone, polysulfone, polyphenylene sulfide, polyvinyl pyrrolidone (PVP), polyethyleneimine (PEI), poly(1-naphthyl methacrylate), poly(vinyl phenyl sulfide) (PVPS), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), poly(N-vinyl phthalimide), polyvinylidene fluoride (PDVF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), silicone materials, and UV-curable materials such as epoxy resins, acrylic resins, acrylate resins, and urethane-based materials.
[0157] Examples of solvents include, but are not limited to, water, ethanol, acetone, and isopropanol.
[0158] In one embodiment, a lighting device includes the device. In another embodiment, a backlight device includes the device. In another embodiment, a display includes the device. In another embodiment, the device is a self-emissive display and does not include a liquid crystal display (LCD). In one embodiment, the display is a micro-LED display, such as a phosphor-converted micro-LED display.
[0159] An apparatus according to the present disclosure includes an LED light source radiatively connected and / or optically coupled to a phosphor composition. Figure 3A-3E An apparatus 10 according to one embodiment of the present disclosure is shown. Figure 3A , the device 10 includes an LED light source 12 and a phosphor composition 14. The LED light source 12 can be a UV or blue light emitting LED. In some embodiments, the LED light source 12 produces blue light with a wavelength range from about 380nm to about 460nm. In the device 10, the phosphor composition 14 is radiation coupled and / or optically coupled to the LED light source 12. Radiation connection or coupling or optical coupling means that the radiation from the LED light source 12 can excite the phosphor composition 14, and the phosphor composition 14 can emit light in response to being excited by the radiation. The phosphor composition 14 can be disposed on a portion or component of the LED light source 12, or positioned at a certain distance away from the LED light source 12. In some embodiments, the device can be a backlight unit for display applications. In other embodiments, the LED light source 12 is a micro-LED, and the device is used for a self-emitting display. Figure 3BAn exemplary embodiment is shown in which the phosphor composition 14 is disposed on the LED light source 12. The LED light source 12 is disposed on a reflective layer 16. The reflective layer 16 reflects light from the LED light source 12 toward the LED light source and the phosphor composition 14. The reflective layer 16 can be any material suitable for reflecting light. In one embodiment, the reflective layer 16 can be a metal layer, such as aluminum, silver, a silver alloy, or an aluminum alloy. Figure 3C An exemplary embodiment is shown in which the phosphor composition 14 is disposed on the LED light source 12. An encapsulation or barrier layer 18 is disposed on the phosphor composition 14. The encapsulation or barrier layer 18 can be a low temperature glass, or a polymer or resin known in the art, such as an epoxy resin, a silicone resin, an epoxy-silicone resin, an acrylate, or a combination thereof. The encapsulation or barrier layer 18 should be transparent to allow light to pass through these elements. Figure 3D An exemplary embodiment is shown in which the LED light source 14 is depicted as an array of LED light sources 12. In some embodiments, the LED light sources 12 are mini-LEDs or micro-LEDs. Figure 3E An exemplary embodiment is shown in which the phosphor composition 14 is located remote from the LED light source 12 , which is depicted as an array of LED light sources 12 .
[0160] The industry trend is and continues to be toward devices that require smaller sized particles. New generation devices use smaller LEDs, such as mini LEDs and micro LEDs. Mini LEDs have a size of about 100 μm to 0.7 mm, while micro LEDs have a size of less than 100 μm. Displays can include miniaturized backlights arranged with individual mini LEDs or micro LEDs, self-luminous phosphor-converted (PC) mini LEDs or micro LEDs, films, and printed inks for preparing the films and LEDs.
[0161] The general discussion of the exemplary LED light sources discussed herein is for light sources based on inorganic LEDs. The most popular white light LEDs are based on blue light emitting or UV GaInN chips. In addition, for inorganic LED light sources, the term LED light source is intended to cover all LED light sources, such as semiconductor laser diodes (LDs), organic light emitting diodes (OLEDs), or a mixture of LEDs and LDs. The LED light source may be a mini LED or micro LED, which may be used for self-emitting displays. In addition, it should be understood that, unless otherwise stated, the LED light source may be replaced, supplemented or enhanced by another radiation source, and any reference to semiconductors, semiconductor LEDs or LED chips represents only any suitable radiation source, including but not limited to LDs and OLEDs.
[0162] The phosphor composition 14 can be present in any form, such as a powder, glass, or a composite, for example a phosphor-polymer composite or a phosphor-glass composite. In addition, the phosphor composition 14 can be used as a layer, a sheet, a film, a strip, dispersed particles, or a combination thereof. In some embodiments, the phosphor composition 14 includes a phosphor composition in the form of a glass. In some of these embodiments, the device 10 may include the phosphor composition 14 in the form of a phosphor wheel (not shown). The phosphor wheel may include a phosphor composition embedded in a glass. Phosphor wheels and related devices are described in WO 2017 / 196779.
[0163] The phosphor composition is optically coupled or radiantly connected to an LED light source. In one embodiment, a white blended light may be obtained by blending a red phosphor material and a green phosphor material with an LED light source, such as a blue light or UV LED.
[0164] Figure 4 A lighting device or lamp 20 according to some embodiments is shown. In one embodiment, the lighting device 20 can be a backlight device. The lighting device 20 includes an LED chip 22 and leads 24 electrically attached to the LED chip 22. The leads 24 can include thin wires supported by a thicker lead frame 26, or the leads 24 can include self-supporting electrodes and the lead frame can be omitted. The leads 24 provide current to the LED chip 22, thereby causing it to emit radiation.
[0165] The phosphor composition layer 30 is disposed on the surface of the LED chip 22. The phosphor layer 30 can be disposed by any suitable method, for example, by applying a film or by using a slurry composition or ink composition (as discussed above) prepared by mixing the phosphor composition and a binder material or solvent. In one such method, a silicone slurry in which phosphor composition particles are randomly suspended or uniformly dispersed is placed around the LED chip 22. This method only illustrates possible positions of the phosphor layer 30 and the LED chip 22. By applying and drying the slurry above the LED chip 22, the phosphor layer 30 can be coated above or directly on the light emitting surface of the LED chip 22. The light emitted by the LED chip 22 is mixed with the light emitted by the phosphor composition to produce the desired emission.
[0166] Continue to refer Figure 4, LED chip 22 can be encapsulated in envelope 28. Encapsulation 28 can be formed of, for example, glass or plastic. LED chip 22 can be surrounded by encapsulation material 32. Encapsulation material 32 can be low temperature glass, or a polymer or resin known in the art, such as epoxy resin, silicone resin, epoxy-silicone resin, acrylate or a combination thereof. In an alternative embodiment, lighting device 20 can include only encapsulation material 32 without envelope 28. Both envelope 28 and encapsulation material 32 should be transparent to allow light to pass through these elements.
[0167] In some embodiments as shown in FIG. 3 , the phosphor composition 33 is dispersed within the encapsulating material 32 rather than Figure 4 The LED chip 22 is shown formed directly on the phosphor composition 33. The phosphor composition 33 can be dispersed within a portion of the encapsulation material 32 or dispersed over the entire volume of the encapsulation material 32. The blue light or UV light emitted by the LED chip 22 is mixed with the light emitted by the phosphor composition 33, and the mixed light is transmitted from the lighting device 20.
[0168] In yet another embodiment, the phosphor composition layer 34 is coated onto the surface of the encapsulant 28 rather than being formed on the LED chip 22, such as Figure 4 As shown, the phosphor layer 34 is coated on the inner surface 29 of the envelope 28, but if desired, the phosphor layer 34 can also be coated on the outer surface of the envelope 28. The phosphor layer 34 can be coated on the entire surface of the envelope 28, or only on the top portion of the inner surface 29 of the envelope 28. The UV / blue light emitted by the LED chip 22 is mixed with the light emitted by the phosphor layer 34, and the mixed light is transmitted. Of course, the phosphor composition can be positioned in any two or all three positions (such as Figure 4-Figure 628) or any other suitable location, such as being separated from, away from or integrated into the LED chip 22 by the envelope 28. In one embodiment, the phosphor layer 34 can be a film and positioned away from the LED chip 22. In another embodiment, the phosphor layer 34 can be a film and disposed on the LED chip 22. In some embodiments, the phosphor layer 34 can be applied to the LED chip 22 as an ink composition. In some embodiments, the phosphor layer 34 can be applied to the LED chip 22 as an ink composition and dried to form a film on the LED chip 22. In some embodiments, the phosphor composition can be a single layer or multiple layers. In some embodiments, the film is a multilayer structure, wherein each layer of the multilayer structure comprises at least one phosphor or quantum dot material. In another embodiment, the device structure includes a phosphor composition layer on the LED chip and a remote layer comprising a quantum dot material. In another embodiment, the device structure includes a phosphor composition layer on the LED chip and a remote layer comprising a quantum dot material and a phosphor material. In another embodiment, the device structure includes a phosphor composition layer on the LED chip and a film comprising a quantum dot material positioned away from the LED chip. In another embodiment, a device structure includes a layer of a phosphor composition on an LED chip and a film comprising a quantum dot material and a phosphor material located away from the LED chip.
[0169] In any of the above structures, the lighting device 20 ( Figure 4-Figure 6 ) may also include a plurality of scattering particles (not shown) embedded in the encapsulation material 32. The scattering particles may include, for example, aluminum oxide, silicon dioxide, zirconium oxide, or titanium dioxide. The scattering particles effectively scatter the directional light emitted from the LED chip 22, preferably with a negligible amount of absorption.
[0170] In one embodiment, Figure 5 or Figure 6 The lighting device 20 shown may be a backlight device. In another embodiment, the backlight device includes a backlight unit 10. Some embodiments include a surface mounted device (SMD) type light emitting diode 50 for backlight applications, such as Fig. 7A , Figure 7B and Figure 7C Reference Fig. 7A , the SMD is of "side-emitting type" and has a light emitting window 52 on a protruding portion of a light directing member 54. The SMD package comprises an LED chip 56 as defined above and a phosphor composition 58 as described herein. Figure 7B A phosphor composition 58 is shown disposed on an LED chip 56. Figure 7C A phosphor composition 58 is shown disposed remotely from the LED chip 56 . Figure 7B and Figure 7CAlso shown are LED chips 56 and light directing members 54 disposed on a reflective layer 59. Reflective layer 59 reflects light from LED chips 56 and light directing members 54 toward phosphor composition 58. Reflective layer 59 can be any material suitable for reflecting light. In one embodiment, reflective layer 59 can be a metal layer, such as silver, aluminum, an aluminum alloy, or a silver alloy.
[0171] In another embodiment, the device may be a direct-lit display.
[0172] The LED light source 12 is disposed on a reflector layer 16. The reflector layer 16 reflects light from the LED light source 12 toward the LED light source and the phosphor composition 14. The reflector layer 16 can be any material suitable for reflecting light. In one embodiment, the reflector layer 16 can be a metal layer, such as silver or a silver alloy.
[0173] By using the phosphor compositions described herein, a device that produces white light for display applications and has a high color gamut and high luminance, such as an LCD backlight unit, can be provided. Alternatively, a device that produces white light for general lighting and has high luminance and high CRI values for a wide range of color temperatures of interest (2000K to 10,000K) can be provided.
[0174] The device of the present disclosure includes lighting equipment and display equipment for general lighting and display applications. The example of display equipment includes liquid crystal display (LCD) backlight unit, TV, computer monitor, vehicle display, laptop computer, computer notebook, mobile phone, smart phone, tablet computer and other handheld devices. In the case where the display is a backlight unit, the phosphor composition can be incorporated into a film, sheet or strip that is coupled to the LED light source for radiation and / or optical coupling, as described in U.S. Patent Application Publication No. 2017 / 0254943. The example of other devices includes colored lamps, plasma screens, xenon excitation lamps, UV excitation marking systems, car headlights, home and theater projectors, laser pumping devices and point sensors. In one embodiment, the device can be a fast response display that does not include LCD. The fast response display can be a self-emitting display including phosphor conversion type (PC) micro-LED. The list of these applications is intended to be merely exemplary rather than exhaustive.
[0175] In some embodiments, the film comprising the phosphor composition can be disposed on a small size LED such as a micro LED or a mini LED. In other embodiments, the film comprises a phosphor having a micron or submicron particle size. In other embodiments, the film comprises nano-sized particles. In one embodiment, the film comprises a Mn having a D50 particle size of less than 20 μm, less than 10 μm, particularly less than 5 μm, more particularly nano-sized. 4+Doped phosphor. In another embodiment, the D50 particle size can be about 1 micron to about 20 microns. In another embodiment, the D50 particle size is about 1 micron to about 15 microns. In another embodiment, the D50 particle size is about 1 micron to about 10 microns. In another embodiment, the D50 particle size is about 1 micron to about 5 microns. In another embodiment, the D50 particle size is about 1 micron to about 3 microns. In another embodiment, the D50 particle size is about 50nm to about 1000nm. In another embodiment, the D50 particle size is about 100nm to about 1000nm. In another embodiment, the D50 particle size is about 200nm to about 1000nm. In another embodiment, the D50 particle size is about 250nm to about 1000nm. In another embodiment, the D50 particle size is about 500nm to about 1000nm. In another embodiment, the D50 particle size is about 750nm to about 1000nm. In another embodiment, the D50 particle size is about 50nm to about 10 microns. In another embodiment, the D50 particle size is about 200nm to about 5 microns. In another embodiment, the D50 particle size is about 250nm to about 5 microns. In another embodiment, the D50 particle size is about 500nm to about 5 microns. In another embodiment, the D50 particle size is about 750nm to about 5 microns. In another embodiment, the D50 particle size is about 750nm to about 3 microns.
[0176] Example
[0177] Example 1
[0178] The method for preparing Mn described in U.S. Patent No. 11,193,059 4+ The process of doping phosphors such as K2SiF6 (PFS) was modified to incorporate higher levels of Mn at smaller particle sizes. The concept we wanted to explore was whether maintaining high saturation levels, but reducing the concentration by lowering the concentration of hydrofluoric acid from 49% to 20% would achieve a high nucleation rate, while at the same time reducing the concentration of the reaction, the nuclei would be less likely to form aggregates, resulting in an overall reduction in particle size.
[0179] A sample phosphor GRC092421ATGA (614) consisting of potassium fluoride dissolved in 20% hydrofluoric acid and PFM and H2SiF6 dissolved in separate 20% hydrofluoric acid solutions was prepared. SEM image of phosphor GRC092421ATGA (614) ( Figure 8 ) showed that, although we were able to obtain primary particles close to micrometer size, the product consisted mainly of aggregates that were not broken up upon sonication.
[0180] Rather than focusing on reducing particle size, we aimed to reduce the degree of aggregation to reduce the effective size of the phosphor without changing the primary particle size. Using methods to reduce the degree of aggregation as a starting point, we aimed to develop methods for preparing phosphor particles between 750nm and 1000nm.
[0181] Throughout these experiments, the acidic aqueous phases remained essentially similar to those we used for GRC092421ATGA (614) consisting of potassium fluoride dissolved in 20% hydrofluoric acid and PFM and H2SiF6 dissolved in separate 20% hydrofluoric acid solutions.We initially proposed to screen various surfactants in addition to hexadecyltrimethylammonium bromide (CTAB).
[0182] We found that surfactants containing oxidizable species such as primary or secondary alcohols or primary or secondary amines were rapidly oxidized in the presence of PFM dopants, resulting in rapid browning of the dopant solution and loss of manganese in the 4+ oxidation state. This led us to focus on CTAB as the primary emulsifier, although we have not yet ruled out emulsifiers based on acidic species such as carboxylates, phosphates, or sulfates. 3,7-Dimethyl-3-octanol was selected as a co-emulsifier to help reduce our CTAB consumption. 3,7-Dimethyl-3-octanol is a natural product containing long alkyl chains typical of surfactants and a tertiary alcohol that resists PFM oxidation. We initially proposed to screen various surfactants in addition to hexadecyltrimethylammonium bromide (CTAB).
[0183] Table 1 contains the formulation and particle size data for our first thirty-five screening runs. In these experiments, the target yield was less than 3 grams of product. Within the parameters studied, we achieved a size range of PFS particles from 20 microns down to 120 nm. There was no clear correlation between any of the parameters studied and particle size. However, when we focused only on particles less than 1 micron in size, we found that the CTAB level was consistently 10 grams and the 3,7-dimethyl-3-octanol levels ranged from 75 mL to 105 mL. When expressed as a mixture, the ratios of the components were 60.8 parts heptane, 26.6 parts 3,7-dimethyl-3-octanol, 2.5 parts CTAB, and 10.1 parts 20% HF (水溶液) , where all parts are by volume, except that CTAB is by weight. This sample GRC062221A has a d(50) of 630 nm, which is very close to our target of 750 nm.
[0184] Table 1: Formulation parameters and particle size data used for screening experiments.
[0185] PCT
[0186] 607692B-WO-1
[0187] (39696-68)
[0188]
[0189] PCT
[0190] 607692B-WO-1
[0191] (39696-68)
[0192]
[0193] PCT
[0194] 607692B-WO-1
[0195] (39696-68)
[0196]
[0197] PCT
[0198] 607692B-WO-1
[0199] (39696-68)
[0200]
[0201] PCT
[0202] 607692B-WO-1
[0203] (39696-68)
[0204]
[0205] PCT
[0206] 607692B-WO-1
[0207] (39696-68)
[0208]
[0209] a) Double emulsion refers to an emulsion that has both PFM solution and KF solution as emulsions and then mixes, and single emulsion is an emulsion of only KF solution
[0210] Using sample GRC06222 1A as a starting point, we continue using Design Expert software to expand our DOE space. An additional 34 experiments were performed to explore the design space, and the reaction scale increased from 3 grams to 20 grams during the study. The formulation and particle size data for this second phase of screening are shown in Table 2. The study included treating the emulsified PFS product with magnesium acetate similar to the method described in U.S. Patent Publication No. 2021101539421 to provide a magnesium fluoride coating. The study drew two important conclusions. First, the minimum particle size tends to be concentrated in the band where the ratio (v / w) of 3,7-dimethyl-3-octanol to CTAB is about 5: 1. For example, 111 mL 3,7-dimethyl-3-octanol: 22 grams of CTAB. Fig. 9 A mixture space contour plot of particle size is shown where CTAB is fixed at 2 parts and the band of minimum particle size is located at about 9 parts of 3,7-dimethyl-3-octanol over a wide range of heptane to hydrofluoric acid (20% HF) ratios.
[0211] Table 2: Results from DOE experiments 2 Recipe parameters and d(50) data for each stage.
[0212] PCT
[0213] 607692B-WO-1
[0214] (39696-68)
[0215]
[0216] PCT
[0217] 607692B-WO-1
[0218] (39696-68)
[0219]
[0220] PCT
[0221] 607692B-WO-1
[0222] (39696-68)
[0223]
[0224] PCT
[0225] 607692B-WO-1
[0226] (39696-68)
[0227]
[0228] PCT
[0229] 607692B-WO-1
[0230] (39696-68)
[0231]
[0232] PCT
[0233] 607692B-WO-1
[0234] (39696-68)
[0235]
[0236] PCT
[0237] 607692B-WO-1
[0238] (39696-68)
[0239]
[0240] a) Single emulsion is an emulsion of only KF solution, slow addition is the slow addition of PFM solution and H2SiF6 solution to KF solution without surfactant
[0241] b) Mineral oil instead of heptane
[0242] c) 20% HF is first saturated with K2SiF6, then KF is added and the solution is filtered
[0243] Second, even when analyzing the quantum efficiency of the samples before the SRP process (see SRP process steps below), a significant portion of the samples had a %QE that was very high and in some cases exceeded 90%. Fig.10 Mixture space contour plots of %QE are shown, where regions of high %QE are found at low 3,7-dimethyl-3-octanol amounts and a heptane to hydrofluoric acid ratio of about 55:30 (v / v). In both contour plots, the range for 3,7-dimethyl-3-octanol extends to 98%, however the maximum level tested does not exceed 13 parts, and all data are constrained to the far left of the plots. Extrapolated curves beyond 13 parts 3,7-dimethyl-3-octanol may have significant errors and should only be used to indicate directionality.
[0244] Several samples in Table 2 were further processed using the SRP process. This process step improved the overall %QE and stability of the phosphor and provided the best quality optical data for further analysis. Table 3 shows selected particle sizes and optical data for the SRP processed samples. As can be seen from the table, many samples were found to have a median particle size between 1 micron and 3 microns, and a QE exceeding 90% and a %Mn dopant exceeding 1.5%.
[0245] Table 3: Particle size and optical properties of PFS after SRP treatment
[0246]
[0247]
[0248] Samples with an E prefix were processed using the emulsion method described in the SOP below. Samples with a GRC prefix, to which no emulsifier or heptane was added, were processed in a similar manner and used as control samples.
[0249] Analysis of the data for these samples revealed several trends. First, the average particle size measured correlated strongly with the % CTAB in the blend formulation, as Fig.11 This trend is completely consistent with the literature data.
[0250] We also found that when the average particle size approaches 1 micron, the particle size distribution becomes bimodal, and both nano-sized particles and micro-sized particles are present in the sample. Fig. 12A The particle size distribution of sample E112421AMgGA (632) with submicron d(50) and bimodal size distribution is shown, and Fig. 12B An SEM of this sample is shown. It is known that there are boundaries within the space of emulsion mixtures where the amount of phase present in solution can change. We suspected that the emulsion mixture was close to a boundary and that our mixture contained both microemulsified droplets that produced nano-sized particles and unstable macroemulsified droplets that produced larger particle sizes.
[0251] Our second finding is that Fig.13 As shown in Figure 2, the amount of manganese dopant incorporated into the PFS product decreases as the amount of CTAB increases. Our previous work showed that when we reduce the PFS particle size, the amount of manganese in the product decreases due to the effect of the washing step that extracts a portion of the manganese from the particle surface. Alternatively, CTAB may act as a solubilizing cation and chelate some of the manganese dopant, preventing it from being incorporated into the product.
[0252] We also found that over a wide range of particle sizes, %QE remained relatively constant between 80% and 100%. This can be explained by Fig.14This is explained by the fact that the drop in Mn dopant concentration shown (which typically results in an increase in %QE) somewhat offsets the normal drop in %QE. Furthermore, the range of values from 80% to 100% is much wider than we typically observe for mature methods, and this noise can mask more subtle trends.
[0253] Characterization techniques
[0254] Optical properties of PFS powders, including QE, transmittance (BT), and reflectance of the material at 631 nm (R631), were measured using silicone tape prepared according to our standard operating procedure (SOP). Particle size analysis of PFS powders was measured using a Horiba particle counter according to the SOP and by scanning electron microscopy (SEM) as required. Span or b80 is a measure of the particle size distribution curve and is defined as:
[0255]
[0256] Where D 50 is the median particle size in the volume distribution, D 90 is the particle size in the volume distribution that is larger than 90% of the particles in the distribution, and D 10 The particle size in the volume distribution that is larger than 10% of the particles in the distribution. Starting from sample E092721AMg (Table 2)
[0257] N-methylpyrrolidone (NMP) replaced isopropyl alcohol (IPA) as the particle size distribution (PSD) analysis solvent to increase the refractive index difference between the solvent and the product, which achieves greater sensitivity to nano-sized materials. The polarity of NMP is also important for improving particle dispersion during measurement. X-ray fluorescence spectroscopy (XRF) and inductively coupled plasma optical emission spectroscopy (ICP-OES) are used to determine the elemental composition of the phosphor materials.
[0258] synthesis
[0259] All construction materials used in the evaluation were used with 49% hydrofluoric acid. All processes were performed in a fume hood. All operators were required to wear HF-resistant safety clothing. The 2-L beaker, stirring paddle, and overhead stirrer were mounted in a secure manner so that the paddle was close to the bottom of the beaker and the entire apparatus was stable at high stirring rates. A plastic emulsifying rotor-stator was mounted adjacent to the stirring paddle.
[0260] In a separate 600mL beaker, add 14.81 grams of potassium fluoride and a magnetic stir bar. Slowly pour in 278mL of 20% HF. Stir the solution until all of the potassium fluoride is completely dissolved, then filter through a paper filter using a plastic Buchner funnel. Transfer the filtered solution to a 2-L reaction beaker. Then add 815mL of heptane, 111mL of 3,7-dimethyl-3-octanol, and 22 grams of CTAB to the reaction beaker. Set the agitator to about 400rpm and set the emulsifier to a high setting to avoid splashing. Add 100mL of the hexafluorosilicic acid stock solution to a separate 100mL beaker.
[0261] Add 1.66 grams of K2MnF6 to a separate 250-mL beaker and add 168 mL of 20% HF. Stir the solution magnetically until the PFM is completely dissolved. Filter the orange solution through a paper filter using a plastic Buchner funnel. Rinse the beaker with water and transfer the filtered PFM solution back to the beaker.
[0262] Using two separate peristaltic pumps, H2SiF6 solution was pumped at 3.1 mL / min and K2MnF6 solution was pumped at 14.1 mL / min into the Mixing T, and then the combined K2MnF6 / H2SiF6 solution was fed into the 2-L beaker. The emulsifier was turned off at the beginning of the addition. When the K2MnF6 solution had finished adding to the 2-L beaker, the hexafluorosilicic acid solution was allowed to add for several more seconds, and then both pumps were stopped.
[0263] Then add 10mL magnesium acetate reaction solution at 2mL / min.After addition is complete, allow stirring for another 10 minutes to allow the reaction to balance.Add 100mL 2-propanol to the reaction vessel to break the emulsion, and stop stirring to separate the emulsion.Decant as much supernatant as possible (about 75% of the volume) and pour the remainder into a 250-mL centrifuge bottle.Pulse centrifuge the bottle for 30 seconds-45 seconds to separate the product.
[0264] The supernatant was discarded and the vial was refilled with the 2-propanol / 20% HF stock solution and shaken vigorously to disperse the product. The product was again isolated by pulse centrifugation.
[0265] The previous steps were repeated, except that the 20% HF treatment solution was used and separated again by pulse centrifugation. The supernatant was discarded and the product was transferred to a 600 mL beaker. The bottle was then filled with 49% HF treatment solution, shaken vigorously to collect the residual product, and poured into a 600 mL beaker. The suspension was stirred for 20 minutes to extract the excess manganese, returned to the centrifuge bottle and separated again by pulse centrifugation.
[0266] Fill the bottle with 20% HF treatment solution and shake vigorously to disperse the product. Isolate the product again by pulse centrifugation. Discard the supernatant and fill the bottle with anhydrous acetone and shake vigorously to disperse the product. Isolate the product again by pulse centrifugation. Repeat the acetone wash and isolation two more times.
[0267] The bottle containing the PFS product moistened with acetone was placed in a desiccator to dry overnight.
[0268] The dried powder was sieved through a clean and dry 60 mesh screen, and any remaining powder lumps were gently pushed through the screen using a brush. The sieved and dried powder was placed in a clean and dry PTFE boat and placed in a drying oven. After purging 3 times with a nitrogen pump, the sample was placed under a vacuum of ~160 ℃ for 2 hours and then allowed to cool to room temperature. The vacuum used was -28in Hg. The sample was bottled immediately after being taken out from the vacuum oven to minimize exposure to moisture.
[0269] Expanding the scale of E112221AMgGA(631)
[0270] Sample E112221AMgGA (631) has a good balance of particle size, quantum efficiency and manganese incorporation (Table 4). In order to process the phosphor into a film, we need to prepare additional materials, so we decided to increase the synthesis scale from 10 grams to 30 grams and perform two synthesis to evaluate reproducibility. For these two experiments, the scale of the prepared solution was tripled. The pump rate of the PFM solution and the H2SiF6 solution was tripled to keep the same addition time, because we are worried that the increased time of pumping more solution will cause the PFM dopant to decompose. We are worried that the increase in pumping rate will make the emulsion unstable and we will observe a significant increase in particle size, but we feel that the decomposition of the dopant is a greater risk. The detailed solution compositions of these experiments are given in Table 4. The detailed scheme of this synthesis is given in the SOP section of this document.
[0271] Table 4: Solutions used to prepare samples E040822AMg and E041222AMg
[0272] Table 4: Solutions used to prepare samples E040822AMg and E041222AMg
[0273]
[0274]
[0275] The results of two scaled-up syntheses are shown in Table 5. We found that while increasing the reaction scale slightly increased the average PFS particle size, it also resulted in a slightly narrower distribution. The quantum efficiency was slightly improved, and the manganese incorporation level was unchanged.
[0276] Table 5: Particle size and optical properties of samples E040822AMg and E041222AMg after SRP treatment
[0277] sample d(50) d(90) %Mn %QE %BT %R631 E112221AMgGA(631) 1.83 3.51 2.3 101 7.9 39 E040822AMgGA(656) 2.2 3.42 2.3 102.1 8.6 35.4 E041222AMgGA(657) 2.21 4.16 2.4 103.4 7.6 37.9
[0278] The samples in Tables 3 and 5 have good particle size, good Mn dopant concentration, and good quantum efficiency. The average particle size of the samples was 1.83 microns for the E112221AMgGA (631) sample, 2.20 microns for the E040822AMgGA (656) sample, and 2.21 microns for the E041222AMgGA (657) sample. The particle size of the three samples was bimodal, including both nano-sized particles and micron-sized particles. Sixty grams of sample E040822AMgGA (656) and sample E041222AMgGA (657) were prepared in two 30 gram batches for use in preparing coatings, films, and inks.
[0279] SOP for the 30 g scale PFS emulsion synthesis of samples E040822AMgGA (656) and E041222AMgGA (657)
[0280] Security
[0281] Hydrofluoric acid and PFS are hazardous materials and all measures should be taken to prevent any exposure. Use appropriate PPE when handling HF, including VITON gloves, TYVEK coat and apron, face shield and safety glasses. Calcium gluconate is in close proximity. Always handle the toxic fluoride powder in a fume hood. Avoid the generation of dust and dust clouds. The material is toxic by inhalation, in contact with skin and if swallowed. Always handle HF and PFS in a fume hood.
[0282] Required Materials
[0283] 188.01.1 Reagents
[0284] 1. Hydrofluoric acid 49% (HF): KMG 49% Or Honeywell HF 49% SLSI.
[0285] 2. Hexafluorosilicic acid (H2SiF6): Alfa Aesar 35% w / w aqueous solution
[0286] 3. Potassium fluoride (KF): Alfa Aesar, anhydrous, 99% crystalline.
[0287] 4. Potassium hexafluorosilicate (K2SiF6): Sigma Aldrich, ≥99.0%.
[0288] 5. Potassium hexafluoromanganate (K2MnF6), recrystallized.
[0289] 6. Hydrogen peroxide 30%.
[0290] 7. Deionized water.
[0291] 8. Acetone: Fisher, Optima grade.
[0292] 9. 2-Propanol
[0293] 10.CTAB
[0294] 11.3,7-Dimethyl-3-octanol
[0295] 12. Heptane
[0296] equipment
[0297] 1. Security:
[0298] a. HF-resistant Viton gloves
[0299] b. Safety glass
[0300] c. Mask
[0301] d.Tyvek jacket
[0302] e.Tyvek apron
[0303] f. Gluconate gel
[0304] 2. Beaker:
[0305] a. 3 peristaltic pumps with narrow tubes (No. 16 for hexafluorosilicic acid and K2MnF6 solutions, No. 14 for Mg acetate solution).
[0306] b. One (1) 4-L polypropylene (PP) or poly(methylpentene) (PMP) plastic beaker.
[0307] i. Polypropylene is more durable, but poly(methylpentene) is transparent and makes the reaction easier to visualize.
[0308] c. One (1) 1-L polypropylene (PP) or poly(methylpentene) (PMP) plastic beaker.
[0309] d. One (1) 500-mL polypropylene (PP) or poly(methylpentene) (PMP) plastic beaker.
[0310] e. One (1) 250-mL polypropylene (PP) or poly(methylpentene) (PMP) plastic beaker.
[0311] 3. Graduated cylinder:
[0312] a. One (1) 500-mL polypropylene
[0313] b. Two (2) 250-mL polypropylene
[0314] 4. The stirring motor is securely attached to the ring stand or other supporting structure.
[0315] 5. PTFE coated impeller - 4 blades, 45° pitch, 4" nominal diameter.
[0316] 6. Plastic Buchner Funnel
[0317] 7. Plastic suction filter bottle
[0318] 8. PTFE filter paper: 143 mm diameter Mitex LS from Fisher Scientific
[0319] 9. Filter paper
[0320] 10.60 mesh plastic screen and mesh.
[0321] 11.PTFE boat
[0322] 12. PTFE coated stirring rod
[0323] 13. Plastic dryer
[0324] 14. Vacuum drying oven with inert atmosphere supply.
[0325] 15. Polypropylene bottles of various sizes
[0326] 16. Cleaning wipes.
[0327] Stock solution
[0328] 1. Hexafluorosilicic acid solution: 22 mL of hexafluorosilicic acid is dissolved in 40 mL of 20% HF
[0329] 2. 20% treatment solution: a saturated solution of potassium hexafluorosilicate (K2SiF6) in 20% hydrofluoric acid (HF), filtered.
[0330] 3.49% treatment solution: a saturated solution of potassium hexafluorosilicate (K2SiF6) in 49% hydrofluoric acid (HF), filtered.
[0331] 4. 20% HF: 20% HF obtained by diluting hydrofluoric acid (49%).
[0332] 5. Propanol washing solution: 20% HF and 2-propanol in a volume ratio of 1:1
[0333] 6. Magnesium acetate solution: 50 g Mg(oAc)2 in 500 mL water.
[0334] program
[0335] (1) Preparation of stock solution
[0336] 1. Prepare a treatment solution of K2SiF6 in 20% HF by adding 55g K2SiF6 to a 1 gallon bottle of 20% HF. Place a new 1 gallon bottle of 20% HF on a stir plate and add a large PTFE coated stir bar. Stir the solution as fast as possible. Slowly add K2SiF6 while maintaining stirring. Stir for 30 minutes. Filter the solution through a PTFE filter and bottle.
[0337] 2. Prepare a treatment solution of K2SiF6 in 49% by adding 155g K2SiF6 to a 1 gallon bottle of 49% HF. Place a new 1 gallon HF bottle on a stir plate and add a large PTFE coated stir bar. Stir the solution as fast as possible. Slowly add the K2SiF6 while maintaining stirring. Stir for 30 minutes. Filter the solution through a PTFE filter and bottle.
[0338] PFS Synthesis
[0339] (1) Synthesis
[0340] 1. Assemble the 4-L beaker, stirring paddle, and overhead stirrer in a secure manner so that the paddle is close to the bottom of the beaker and the entire apparatus is stable at high stirring rates. Install the plastic emulsification rotor-stator adjacent to the stirring paddle. This is the reaction beaker.
[0341] 2. In a separate 1-L beaker add 44.44 g of potassium fluoride and a magnetic stir bar. Slowly pour in 675 mL of 20% HF. Stir until all of the potassium fluoride is completely dissolved. Filter through a paper filter using a plastic Buchner funnel. Transfer the filtered solution to the reaction beaker.
[0342] 3. Add 2444 mL of heptane to the reaction beaker.
[0343] 4. Add 333 mL of 3,7-dimethyl-3-octanol to the reaction beaker.
[0344] 5. Add 66.67 grams of CTAB to the reaction beaker.
[0345] 6. Turn on the agitator to about 500 rpm and set the emulsifier to a high setting to avoid splashing.
[0346] 7. Pour 120 mL of hexafluorosilicic acid stock solution into a 250 mL beaker.
[0347] 8. Weigh 5.0 g of K2MnF6 into a 500-mL beaker. Add 444 mL of 20% HF. Add a magnetic stir bar and stir until completely dissolved. Filter through a paper filter using a Buchner funnel. Rinse the beaker with water and transfer the filtered solution back to the beaker.
[0348] 9. Arrange the beakers of hexafluorosilicic acid and K2MnF6 and the peristaltic pumps so that the solutions flow into a waste container. The H2SiF6 solution is pumped at 9.3 mL / min, while the K2MnF6 solution is pumped at 42.3 mL / min. Prime both pumps.
[0349] 10. Start feeding the solution into the waste beaker, then transfer the line to the mixing T to combine the H2SiF6 solution and the K2MnF6 solution, and feed the combined H2SiF6 / K2MnF6 solution into the reaction beaker while stirring at the maximum rate possible without splashing.
[0350] 11. Turn off the emulsifier.
[0351] 12. When the K2MnF6 has finished adding to the reaction beaker, allow the hexafluorosilicic acid solution to add for an additional 10 seconds and then stop both pumps.
[0352] 13. Place the tubing from the third pump over the reaction vessel and pump 15 ml of the magnesium acetate reaction solution at 6 mL / min. When finished, make sure the pumps are all turned off and set all tubing aside. Make sure to flush the tubing with deionized water before storage.
[0353] 14. Stir the reaction vessel for 5 minutes.
[0354] 15. Add 100 mL - 150 mL of 2-propanol to the reaction vessel to break the emulsion and then stop stirring. Allow the solution to separate.
[0355] 16. Decant as much supernatant as possible (approximately 75% of the volume) and pour the remainder into a 250-mL centrifuge bottle.
[0356] 17. Pulse centrifuge for 30 seconds to 45 seconds (maximum rpm = 5000 rpm) to separate the product.
[0357] (2) Processing step 1
[0358] 18. Discard supernatant and fill bottle with 2-propanol / 20% HF stock solution. Shake or stir vigorously to disperse product.
[0359] 19. Repeat the pulse centrifugation.
[0360] 20. Discard the supernatant and fill the bottle with 20% HF treatment solution. Shake or stir vigorously to disperse the product.
[0361] 21. Repeat the pulse centrifugation.
[0362] 22. Discard the supernatant and transfer the product to a 600 mL beaker. Fill the bottle with 49% HF treatment solution. Shake or stir vigorously to collect the residual product. Pour the suspension into a beaker. Stir the suspension for 20 minutes to extract the excess manganese. Return the suspension to the centrifuge bottle.
[0363] 23. Repeat the pulse centrifugation.
[0364] 24. Discard the supernatant. If the supernatant is dark orange, repeat steps 21 and 22.
[0365] 25. Fill the bottle with 20% HF treatment solution. Shake or stir vigorously to disperse the product.
[0366] 26. Repeat the pulse centrifugation.
[0367] 27. Discard the supernatant and fill the bottle with anhydrous acetone. Shake or stir vigorously to disperse the product.
[0368] 28. Repeat pulse centrifugation. Repeat steps 26 and 27 a total of 3 times.
[0369] (3) Separation
[0370] 29. Transfer the bottles to a desiccator to dry overnight.
[0371] 30. Sieve the powder through a clean, dry 60-mesh screen. Use a brush to gently push any remaining powder lumps through the screen.
[0372] 31. The dried powder was placed in a clean and dry PTFE boat and placed in a drying oven. After purging 3 times with a nitrogen pump, the sample was heated to ~160°C under vacuum for 2 hours and then allowed to cool to room temperature before purging the vacuum. The vacuum used was -28 in Hg.
[0373] 32. Bottle the samples immediately to minimize exposure to moisture.
[0374] (4) SRP process
[0375] 33. Anneal the sample at 540°C for 8 hours in 20% F2 / 80% N2. Press the sample into a boat.
[0376] 34. After annealing, scrape the outside of the filter cake to remove copper contamination.
[0377] 35. Bottle the samples immediately to minimize exposure to moisture.
[0378] Example 2
[0379] In the following samples, 3,7-dimethyl-3-octanol (Product No. 309915) from Sigma-Aldrich was purified by fractional distillation prior to use. The pre-distillate below 180°C showed phase separation and was therefore discarded. The middle fraction boiling at about 180°C was collected and used in these experiments.
[0380] Sample 1 (E112222ATMgGA(762)):
[0381] 14.8g KF is dissolved in 675mL 20% HF, then this solution is added in the mixture of 2400mL heptane, 66g CTAB and 330mL 3,7-dimethyl-3-octanol, and uses impeller to continuously mix to form potassium-containing emulsion.In two separate beakers, prepare K2MnF6(6.9g) solution in 20% HF (445mL) and H2SiF6 solution in 20% HF (H2SiF6:20% HF volume ratio is 22mL:40mL).K2MnF6 solution has a large amount of undissolved materials, and this material is removed by vacuum filtration.Use two separate peristaltic pumps, by K2MnF6 and H2SiF6 two kinds of solutions are combined in mixing T, then the combined K2MnF6 / H2SiF6 solution is fed in the emulsion, mixes with 800rpm. The pumping rates of K2MnF6 solution and H2SiF6 solution were 44.7 mL / min and 12.8 mL / min, respectively.
[0382] Sample 2 (E112222BTMgGA(763)):
[0383] 44g KF is dissolved in 675mL 20% HF, then the solution is added to 2400mL heptane, 66g CTAB and 330mL 3,7-dimethyl-3-octanol mixture, and use impeller to continuously mix to form potassium-containing emulsion.In two separate beakers, prepare K2MnF6 (5g) solution in 20% HF (445mL) and H2SiF6 solution in 20% HF (H2SiF6:20% HF volume ratio is 22mL:40mL).Use two separate peristaltic pumps, by K2MnF6 and H2SiF6 two kinds of solutions are combined in mixing T, then the combined K2MnF6 / H2SiF6 solution is fed in the emulsion, mixed with 800rpm.The pumping rate of K2MnF6 solution and H2SiF6 solution is respectively 44.7mL / min and 9.5mL / min.
[0384] Sample 3 (E112322RTMgGA(763)):
[0385] 44g KF is dissolved in 675mL 20% HF, then the solution is added to 2400mL heptane, 66g CTAB and 330mL 3,7-dimethyl-3-octanol mixture, and use impeller to continuously mix to form potassium-containing emulsion.In two separate beakers, prepare K2MnF6 (5g) solution in 20% HF (445mL) and H2SiF6 solution in 20% HF (H2SiF6:20% HF volume ratio is 22mL:40mL).Use two separate peristaltic pumps, by K2MnF6 and H2SiF6 two kinds of solutions are combined in mixing T, then the combined K2MnF6 / H2SiF6 solution is fed in the emulsion, mixed with 800rpm.The pumping rate of K2MnF6 solution and H2SiF6 solution is respectively 44.7mL / min and 9.5mL / min.
[0386] Sample 4 (E122722ATMgGA(767)):
[0387] 44g KF is dissolved in 675mL 20% HF, then the solution is added to 2400mL heptane, 66g CTAB and 330mL 3,7-dimethyl-3-octanol mixture, and use impeller to continuously mix to form potassium-containing emulsion.In two separate beakers, prepare K2MnF6 (5g) solution in 20% HF (445mL) and H2SiF6 solution in 20% HF (H2SiF6:20% HF volume ratio is 22mL:40mL).Use two separate peristaltic pumps, by K2MnF6 and H2SiF6 two kinds of solutions are combined in mixing T, then the combined K2MnF6 / H2SiF6 solution is fed in the emulsion, mixed with 800rpm.The pumping rate of K2MnF6 solution and H2SiF6 solution is respectively 44.7mL / min and 9.5mL / min.
[0388] Purification of samples 1-4
[0389] Then add 15ml magnesium acetate reaction solution at 2mL / min.After addition is complete, allow stirring for another 10 minutes to make the reaction equilibrium.100mL 2-propanol is added to the reaction vessel to break up the emulsion, and stirring is stopped to separate the emulsion.Decant as much supernatant as possible (about 75% of the volume) and pour the remainder into a 250-mL centrifuge bottle.Pulse centrifuge the bottle for 30 seconds-45 seconds to separate the product.
[0390] The supernatant was discarded, a Teflon stir bar was added to each bottle and the bottles were refilled with the 2-propanol / 20% HF stock solution and shaken vigorously to disperse the product. The product was again isolated by pulse centrifugation.
[0391] Repeat the previous steps, except that the 20% HF treatment solution is used and separated again by pulse centrifugation. The supernatant is discarded. The bottle is then filled with the 49% HF treatment solution and shaken vigorously. The suspension is stirred for 20 minutes to extract the excess manganese, returned to the centrifuge bottle and separated again by pulse centrifugation.
[0392] Fill the bottle with 20% HF treatment solution and shake vigorously to disperse the product. Isolate the product again by pulse centrifugation. Discard the supernatant and fill the bottle with anhydrous acetone and shake vigorously to disperse the product. Isolate the product again by pulse centrifugation. Repeat the acetone wash and isolation two more times.
[0393] The bottle containing the PFS product moistened with acetone was placed in a desiccator to dry overnight.
[0394] The dried powder was sieved through a clean and dry 60 mesh screen, and any remaining powder lumps were gently pushed through the screen using a brush. The sieved and dried powder was placed in a clean and dry PTFE boat and placed in a drying oven. After purging 3 times with a nitrogen pump, the sample was placed under a vacuum of ~160 ℃ for 2 hours and then allowed to cool to room temperature. The vacuum used was -28in Hg. The sample was bottled immediately after being taken out from the vacuum oven to minimize exposure to moisture.
[0395] The data of PFS powders of samples 1-4 are shown in Table 6. Scanning electron micrographs of samples 1-3 are shown in Figure 15-17 middle.
[0396] Table 6 Quantum efficiency, composition and particle size data of samples 1-4
[0397]
[0398] Samples 1-4 have very small D50 particle size. The quantum efficiency (QE) values of each sample are very good. All QE values are over 85%. The permeation (BT) measurement results and Mn incorporation (%Mn) are good. Samples 2 and 4 have QE values over 100%, Mn incorporation over 2%, and very small particle size, and the D50 particle size is 2.43 μm and 2.324 μm, respectively.
[0399] Example 3
[0400] Sample A052022BT was prepared as follows: Ethyl cellulose (1 g) was dissolved in acetone (37.7 g) to form a gel. 19 g of KF crystals were added to the gel under stirring. The mixed gel was then vacuum dried at room temperature for 1 day to produce a KF gel with an ethyl cellulose coating. K2MnF6 (1.6834 g) was dissolved in 49% HF (72 mL) and then 45% H2SiF6 (7.28 mL) was added under continuous stirring. The KF gel with an ethyl cellulose coating (15.2 g) was added to the stirred solution and stirred for about 15 minutes. The resulting mixture was centrifuged and the resulting solid was washed with the following solutions with centrifugation between each wash: 150 mL 1:1 volume mixture of isopropanol and 20% HF; 150 mL 20% HF saturated with K2SiF6; 150 mL 49% HF saturated with K2SiF6; 100 mL 20% HF; ethanol (twice); acetone (twice). The sample was vacuum dried overnight. Table 7 shows the particle size distribution and quantum efficiency of the resulting micron-sized PFS powder.
[0401] Table 7
[0402]
[0403] Example 4-Example 7
[0404] Example 4: Ionic Strength of Na Precursor Solution
[0405] Solution A was prepared by slowly adding 58 g CH3COONa to a polypropylene beaker containing 140 mL DI water. Solution B was prepared by adding 32.9 mL 45% H2SiF6 and 12.36 g K2MnF6 to 330 mL 49% HF in a 600 mL polypropylene beaker. The contents of beaker A were quickly poured into solution B and the resulting suspension was stirred for 3 minutes. Stirring was stopped, the supernatant was decanted, the slurry was centrifuged and washed in an almost saturated solution of K2SiF6 in 49% HF for 15 minutes. After the 15-minute washing step, stirring was stopped, the supernatant was decanted, and the slurry was centrifuged, rinsed once with 100 mL 20% HF and rinsed three times with 100 mL acetone. The solid was dried under vacuum for more than 30 minutes and then annealed at 540° C. for 8 hours under a 20% fluorine: 80% nitrogen atmosphere. The annealed powder was sieved through an 80 mesh sieve.
[0406] Solution B remained unchanged, while in solution A, CH3COONa was replaced by NaF, NaF+HF, NaCF3CO2, NaClO4 Na6[(PO3)6], or Na2SO4. It was found that the particle size from these Na source replacement experiments was strongly correlated with the ionic strength of solution A, as shown in Table 1.
[0407] Table 8. Results for samples from different Na precursors
[0408]
[0409]
[0410] *The formula used to calculate the ionic strength in this table is: where c i is the molar concentration of ion I, z i is the charge of the ion
[0411] Example 5: Na molar ratio
[0412] Solution B remained unchanged, while in solution A, the molar ratio of Na to Si was varied from 2 to 7. There was a trend between particle size and Na molar ratio when the amount of Na was above 4. When the amount of Na was below 4, the reaction system was sensitive to many parameter changes such as Mn doping level, surfactant or even scale-up.
[0413] Table 9. Results from samples with different Na to Si molar ratios
[0414]
[0415] Example 6: Using an ice bath to reduce NSF solubility
[0416] The variation in this example is to place the reaction system in an ice bath. Lowering the reaction temperature affects the solubility of the precursors, supersaturation conditions, and therefore the nucleation of particle growth.
[0417] Table 10. Results for samples from ice bath
[0418]
[0419] Example 7: Increasing Na moles to promote Mn incorporation
[0420] The variation in this example is to place the reaction system in an ice bath. Lowering the reaction temperature affects the solubility of the precursors, supersaturation conditions, and therefore the nucleation of particle growth.
[0421] Table 11. Results for samples from ice bath
[0422]
[0423] Example 8-Example 12
[0424] Example 8 (Sample I-09):
[0425] 1. Solution A: 1.976 g K2MnF6 was dissolved in 24 mL 55% HF solution and then added to 265 mL of treatment solution (0.17 M K2SiF6 in 49% HF) with stirring.
[0426] 2. Solution B: 76.8 mL of bis(2-ethylhexyl)phosphate was added to 920 mL of di(propylene glycol) dimethyl ether under stirring.
[0427] 3. Solution A was added to solution B with stirring, the mixture was slowly stirred for an additional 10 minutes, and the resulting PFS solid was collected by centrifugation at 6000 rpm for 1 minute.
[0428] 4. The solid was redispersed in 80 mL of treatment solution and then centrifuged again. This process was repeated twice.
[0429] 5. The solid was then redispersed in 250 mL of a 20% ethanol / 80% acetone mixture and centrifuged again. This process was repeated three times.
[0430] 6. Finally the solid was dried in a vacuum chamber at room temperature overnight and then dried in an oven at 100°C to give ~11.7 g of yellow powder.
[0431] Table 12 shows the dynamic laser scattering particle size distribution data and quantum efficiency data of the powder. The scanning electron micrograph of the synthesized sample of Example 8 is shown in Fig.18 middle. Fig.19 Shown is the reflectance IR spectrum of the PFS powder which indicates the presence of the organophosphate surfactant.
[0432] Additional powders were synthesized at different volumes of di(propylene glycol) dimethyl ether to observe the effect of antisolvent volume on PFS:Mn 4+ Effect of particle size.
[0433] Embodiment 9 (A110822AT):
[0434] Potassium hexafluoromanganate (K2MnF6, 0.8429g) is dissolved in 74mL 20% HF. 5.56mL fluorosilicic acid (H2SiF6) is added to the solution. After short mixing, the solution is filtered. The filtered solution is solution A. Potassium fluoride (7.4g) is dissolved in 20% HF (139mL) in a separate beaker, and then di(propylene glycol) dimethyl ether (400mL) is added under stirring to prepare solution B. Solution A is quickly added to solution B at 400rpm stirring. After precipitation, stirring speed is reduced to 250rpm and the suspension is stirred for 10 minutes. After stopping stirring, the supernatant is decanted, and the product is centrifuged at 4000rpm. After centrifugation, the supernatant was decanted again, and the product was washed with 15 mL of 20% HF, then washed with a 20% HF solution saturated with potassium hexafluorosilicate (K2SiF6), and centrifuged and decanted between washes. The product was then suspended in 50 mL of a 49% HF solution saturated with K2SiF6 for 8 minutes. After centrifugation and decanting, the product was washed with 50 mL of a 20% HF solution saturated with K2SiF6, then washed with 50 mL of ethanol, and then washed three times with acetone (75 mL each time). The product was dried under vacuum at room temperature. Figure X The obtained submicron PFS:Mn 4+ Scanning electron micrograph of the powder, which shows that most particles are <1.0 μm in diameter. Table 12 shows the dynamic laser scattering particle size distribution data and quantum efficiency data for the powder.
[0435] The scanning electron micrograph of the synthesized sample of Example 9 is shown in Fig. 20 middle.
[0436] Example 10 (A021523BTMgGA (782)):
[0437] Phosphoric acid (2.5mL, 85%) is added to 100mL of 49% HF solution saturated with K2SiF6 and stirred at 300rpm. Then, a solution of K2MnF6 (0.8258g) dissolved in 49% HF (14mL) is added to the K2SiF6 solution. The solution is solution A. Acetone (114mL) is quickly added to solution A at a stirring rate of 550rpm. After precipitation, the stirring rate is reduced to 240rpm and continued to mix for 4 minutes. While stirring, 3.0mL of Mg acetate solution (1g Mg acetate / 10mL water) is added dropwise to the suspension. After the addition of Mg acetate is completed, stirring is continued for 4 minutes. Stop stirring, decant the supernatant, and the suspension is centrifuged at 2000rpm for 1 minute. After decanting the supernatant, the product is washed with 50mL 20% HF, and the supernatant is subsequently centrifuged and decanted. The product was suspended in 50 mL of 49% HF saturated with K2SiF6 and kept under stirring for 14 minutes. After centrifugation and decanting, the product was washed with 50 mL of isopropanol / 20% HF (1:1 volume) solution and then washed three times with acetone (50 mL). The product was dried in a vacuum dryer at room temperature overnight. The resulting powder was sieved through a 60 mesh screen and then heated in vacuum at ~160°C for about 3.5 hours. The dried powder was annealed at 540°C in an atmosphere of 20% F2 / 80% N2 for 8h. Table 12 shows that the product is mainly composed of submicron PFS:Mn 4+ The particle size distribution and quantum efficiency data of the sample are presented.
[0438] Example 11 (A022423ATMgGA (783)):
[0439] Acetone (114 mL), a saturated solution of KF in 49% HF (1.28 mL), and deionized water (38 mL) were combined in a beaker under stirring to obtain solution A. In a separate beaker, phosphoric acid (85%, 2.5 mL) was added to 49% HF (100 mL) saturated with K2SiF6. A solution of K2MnF6 (0.8264 g) dissolved in 49% HF (14 mL) was added, followed by the K2SiF6 solution to obtain solution B. While stirring at 550 rpm, solution B was quickly added to solution A. After precipitation, the stirring rate was reduced to 240 rpm and mixing was continued for 4 minutes. While stirring, 3.0 mL of Mg acetate solution was added dropwise to the suspension. After the addition of Mg acetate was completed, stirring was continued for 4 minutes. Stirring was stopped, the supernatant was decanted, and the suspension was centrifuged at 2000 rpm for 1 minute. After decanting the supernatant, the product was washed with 50 mL of 20% HF, and the supernatant was subsequently centrifuged and decanted. The product was suspended in 50 mL of 49% HF saturated with K2SiF6 and kept under stirring for 15 minutes. After centrifugation and decanting, the product was washed with 50 mL of isopropanol / 20% HF (1:1 volume) solution and then washed three times with acetone (50 mL). The product was dried in a vacuum dryer at room temperature for approximately 4 h. The resulting powder was sieved through a 60 mesh screen and then heated in vacuum at ~160°C for approximately 3.5 hours. The dried powder was annealed at 540°C in an atmosphere of 20% F2 / 80% N2 for 8 h. Table 12 shows that the product is mainly composed of submicron PFS:Mn 4+ The particle size distribution and quantum efficiency data of the sample are presented.
[0440] Example 12 (A022723CTMgGA (783)):
[0441] Acetone (55 mL), a saturated solution of KF in 49% HF (7.66 mL), and deionized water (57.5 mL) were combined in a beaker under stirring to give solution A. In a separate beaker, 49% HF (100 mL) saturated with K2SiF6 was added to a solution of K2MnF6 (0.8241 g) dissolved in 49% HF (14 mL) to give solution B. Solution B was quickly added to solution A while stirring at 550 rpm. After precipitation, the stirring rate was reduced to 240 rpm and mixing was continued for 4 minutes. While stirring, 3.0 mL of Mg acetate solution was added dropwise to the suspension. After the addition of Mg acetate was complete, stirring was continued for 4 minutes. The remaining sample washing, separation, drying, and annealing steps were performed as described in Example 11. Table 12 shows the composition of the PFS:Mn, which is mainly composed of submicron PFS:Mn 4+ The particle size distribution and quantum efficiency data of the sample are presented.
[0442] Example 13 (A030723ATMgGA (784))
[0443] Acetone (34 mL), a saturated solution of KF in 49% HF (8.72 mL), and deionized water (45.0 mL) were combined in a beaker with stirring to give Solution A. In a separate beaker, 49% HF (100 mL) saturated with K2SiF6 was added to a solution of K2MnF6 (0.8270 g) dissolved in 49% HF (14 mL) to give Solution B. Solution A was quickly added to Solution B while stirring at 550 rpm. The rest of the sample preparation, washing, separation, drying, and annealing were performed as described in Example 12. Table 12 shows that the PFS:Mn was composed mainly of micron-sized 4+ Particle size distribution, %Mn as determined by elemental analysis (ICP), and quantum efficiency data for this sample of composition.
[0444] Example 14 (A030823ATMgGA (784))
[0445] Acetone (11.5 mL), a saturated solution of KF in 49% HF (8.72 mL), and deionized water (27.0 mL) were combined in a beaker with stirring to give Solution A. In a separate beaker, 49% HF (100 mL) saturated with K2SiF6 was added to a solution of K2MnF6 (0.8312 g) dissolved in 49% HF (14 mL) to give Solution B. Solution A was quickly added to Solution B while stirring at 550 rpm. The rest of the sample preparation, washing, separation, drying, and annealing were performed as described in Example 12. Table 12 shows that the PFS:Mn was composed primarily of micron-sized 4+ Particle size distribution, %Mn as determined by elemental analysis (ICP), and quantum efficiency data for this sample of composition.
[0446] Example 15 (A041723ATMg)
[0447] Acetone (125 mL), a saturated solution of KF in 49% HF (47.5 mL) and 20% HF (103.5 mL) were combined in a beaker under stirring to obtain solution A. In a separate beaker, K2MnF6 (1.9301 g) was dissolved in 49% HF (60 mL) under stirring until K2MnF6 was completely dissolved. 45% H2SiF6 (9.24 mL) was quickly added to the solution to form solution B. Then, solution B was quickly added to solution A at 600 rpm. After precipitation, the stirring speed was reduced to 380 rpm and mixing was continued for 4 minutes. While stirring, 5.60 mL of Mg acetate solution (1 g Mg acetate in 10 mL water) was added dropwise to the suspension. After the addition of Mg acetate was completed, stirring was continued for 4 minutes. Stirring was stopped, the supernatant was decanted, and the suspension was centrifuged at 2000 rpm for 1 minute. After decanting the supernatant, the product was washed with 100 mL of 20% HF, and the supernatant was subsequently centrifuged and decanted. The product was suspended in 100 mL of 49% HF saturated with K2MnF6 and kept under stirring for 15 minutes. After centrifugation and decanting, the product was washed with 100 mL of isopropanol / 20% HF (1:1 volume) solution and then washed three times with acetone (10 mL). The product was dried in a vacuum dryer at room temperature overnight. The resulting powder was sieved through a 60 mesh screen and then heated in vacuum at ~160°C for about 3.5 hours. Table 12 shows that the PFS:Mn mainly consists of micron-sized 4+ Particle size distribution, %Mn as determined by elemental analysis (ICP), and quantum efficiency data for this sample of composition.
[0448] Example 16 (A041723BTMg)
[0449] Acetone (167 mL), a saturated solution of KF in 49% HF (47.5 mL), and 20% HF (108 mL) were combined in a beaker under stirring to give Solution A. In a separate beaker, K2MnF6 (1.9347 g) was dissolved in 49% HF (60 mL) under stirring until K2MnF6 was completely dissolved. To this solution, 45% H2SiF6 (9.24 mL) was quickly added to form Solution B. Solution B was then quickly added to Solution A at 600 rpm. After precipitation, the stirring rate was reduced to 380 rpm and mixing was continued for 4 minutes. The rest of the sample preparation, washing, separation, and drying were performed as described in Example 15. Table 12 shows that the PFS:Mn, which is mainly composed of micron-sized 4+ Particle size distribution, %Mn as determined by elemental analysis (ICP), and quantum efficiency data for this sample of composition.
[0450] Table 12. Particle size distribution and quantum efficiency of samples dispersed in N-methyl-2-pyrrolidone (NMP).
[0451]
[0452]
[0453] The powders were synthesized in different volumes of di(propylene glycol) dimethyl ether (proglyme) to observe the effect of antisolvent volume on PFS:Mn 4+ Effect of particle size. Fig.21 The volume of Proglyme (antisolvent) used in the synthesis is compared to PFS:Mn 4+ Plot of particle size D50 (μm). Fig.21 The particle size decreases at higher volumes of antisolvent, indicating that the antisolvent volume can be used to change the PFS:Mn 4+ Particle size. Fig. 22 Is PFS:Mn 4+ Particle size D50 (μm) versus quantum efficiency (QE, %). 4+ The quantum efficiency of the samples was similar regardless of particle size.
[0454] This written description uses examples, including the best mode, and also enables any person skilled in the art to practice the invention, including making and using any devices or systems and performing any incorporated methods. The patentable scope of the invention is defined by the claims, and may include other examples that occur to those skilled in the art. Such other examples are intended to be within the scope of the claims if they have structural elements that do not differ from the literal language of the claims, or if they include equivalent structural elements with insubstantial differences from the literal language of the claims.
Claims
1. A method for preparing a Mn4+-doped phosphor of formula I, A x [MF y ]:Mn 4+ I The method includes combining a first aqueous solution comprising a source of Mn with a second solution comprising H2MF6 to form a third solution, and combining the third solution with a fourth solution comprising a source of A to form the Mn 4+ Doped phosphors, wherein A is Li, Na, K, Rb, Cs, or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd, or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
2. The method according to claim 1, wherein the Mn of formula I 4+ The doped phosphor is selected from the group consisting of: K2[SiF6]:Mn 4+ 、K2[TiF6]:Mn 4+ 、K2[SnF6]:Mn 4+ 、Cs2[TiF6]:Mn 4+ 、Rb2[TiF6]Mn 4+ 、Cs2[SiF6]:Mn 4+ 、Rb2[SiF6]:Mn 4+ 、Na2[SiF6]:Mn 4+ 、Na2[TiF6]:Mn 4+ 、Na2[ZrF6]:Mn 4+ 、K3[ZrF7]:Mn 4+ 、K3[BiF6]K3[YF6]:Mn 4+ 、K3[LaF6]:Mn 4+ 、K3[GdF6]:Mn 4+ 、K3[NbF7]:Mn 4+ and K3[TaF7]:Mn 4+ .
3. The method according to claim 1, wherein the phosphor of formula I is K2SiF6:Mn 4+ or Na2[SiF6]:Mn 4+ . The method of claim 1 , wherein the first aqueous solution further comprises aqueous HF.
5. The method of claim 1, wherein the Mn source is selected from the group consisting of K2MnF6, Na2MnF6, KMnO4, K2MnCl6, MnF4, MnF3, MnF2, MnO2, and combinations thereof.
6. The method of claim 4, wherein the Mn source is K2MnF6.
7. The method of claim 1, wherein the H2MF6 is H2SiF6.
8. The method of claim 1, wherein the source of A is one or more compounds selected from the group consisting of KF, KHF2, KC6H7O7, KOH, KCl, KBr, KI, KHSO4, KOCH3, K2S2O8, K2CO3, sodium acetate, NaF, NaCF3CO2, NaClO4, Na6(PO3)6 and NaSO4.
9. The method of claim 1, wherein the source of A is KF or NaF.
10. The method of claim 9, wherein the KF is coated with an acid degradable polymer.
11. The method of claim 1, wherein the fourth solution further comprises hexadecyltrimethylammonium bromide and 3,7-dimethyl-3-octanol.
12. The method of claim 1, wherein the third solution and the fourth solution are combined at a temperature of about 0°C to about -20°C.
13. The method of claim 1, wherein the fourth solution further comprises a ligand.
14. The method according to claim 1, further comprising coating the Mn with CaF2 4+ The phosphor is doped to form a shell and the shell is coated with oleic acid.
15. The method of claim 1, wherein the method is prepared using a microfluidic device.
16. A method for preparing Mn of formula I 4+ Method of doping phosphors, A x [MF y ]:Mn 4+ I The method comprises combining an aqueous solution comprising a Mn source and A2SiF6 with an anti-solvent solution comprising an anti-solvent to form the Mn 4+ Doped phosphors, wherein A is H, Li, Na, K, Rb, Cs, or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd, or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
17. The method of claim 16, wherein the Mn source is selected from the group consisting of K2MnF6, Na2MnF6, KMnO4, K2MnCl6, MnF4, MnF3, MnF2, MnO2, and combinations thereof.
18. The method of claim 16, wherein the Mn source is K2MnF6 and A2SiF6 is K2SiF6 or H2SiF6.
19. The method of claim 16, wherein the antisolvent solution further comprises one or more of HF, water, a potassium source, and one or more surfactants.
20. The method of claim 19, wherein the antisolvent comprises di(propylene glycol) dimethyl ether, isopropanol, ethanol, or acetone, and the surfactant comprises an organophosphate.
21. A method for preparing Na2SiF6:Mn 4+ A method comprising combining (i) an aqueous solution comprising a Mn source and H2SiF6 with (ii) a solution comprising a Na source to form the Na2SiF6:Mn 4+ Phosphor.
22. The method of claim 21, wherein the Mn source is selected from the group consisting of K2MnF6, Na2MnF6, KMnO4, K2MnCl6, MnF4, MnF3, MnF2, MnO2, and combinations thereof, and the Na source is selected from the group consisting of sodium acetate, NaF, NaCF3CO2, NaClO4, Na6(PO3)6, and NaSO4.
23. The method of claim 21, wherein the solutions in (i) and (ii) are combined at a temperature of about 0°C to about -20°C.
24. A Mn of formula I 4+ Doped phosphors, A x [MF y ]:Mn 4+ I wherein the phosphor has a D50 particle size of less than 5 μm and a Mn content of at least 1.5 wt %, wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
25. A Mn of formula I 4+ Doped phosphors, A x [MF y ]:Mn 4+ I wherein the phosphor has an organic phosphate surface coating and a D50 particle size of less than 5 μm, wherein A is Li, Na, K, Rb, Cs, or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd, or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
26. Mn of formula I according to claim 24 or 26 4+ The doped phosphor, wherein the Mn of formula I 4+ The doped phosphor is selected from the group consisting of: K2[SiF6]:Mn 4+ 、K2[TiF6]:Mn 4+ 、K2[SnF6]:Mn 4+ 、Cs2[TiF6]:Mn 4+ 、Rb2[TiF6]Mn 4+ 、Cs2[SiF6]:Mn 4+ 、Rb2[SiF6]:Mn 4+ 、Na2[SiF6]:Mn 4+ 、Na2[TiF6]:Mn 4+ 、Na2[ZrF6]:Mn 4+ 、K3[ZrF7]:Mn 4+ 、K3[BiF6]K3[YF6]:Mn 4+ 、K3[LaF6]:Mn 4+ 、K3[GdF6]:Mn 4+ 、K3[NbF7]:Mn 4+ and K3[TaF7]:Mn 4+ .
27. Mn of formula I according to claim 24 or 26 4+ doped phosphor, wherein the phosphor of formula I is K2SiF6:Mn 4+ or Na2[SiF6]:Mn 4+ .
28. A device comprising an LED light source optically coupled and / or radiantly connected to a phosphor composition comprising a Mn of formula I 4+ Doped phosphors, A x [MF y ]:Mn 4+ I wherein the phosphor has a D50 particle size of less than 5 μm and a Mn content of at least 2.0 wt %, wherein A is Li, Na, K, Rb, Cs, or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd, or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
29. A device comprising an LED light source optically coupled and / or radiantly connected to a phosphor composition comprising a Mn of formula I 4+ Doped phosphors, A x [MF y ]:Mn 4+ I。 wherein the phosphor has a D50 particle size of less than 5 μm and an organic phosphate surface coating, wherein A is Li, Na, K, Rb, Cs, or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd, or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
30. The device according to claim 28 or 29, wherein the LED light source is a UV emitting LED or a blue emitting LED.
31. The device according to claim 28 or 29, wherein the Mn 4+ The doped phosphor is selected from the group consisting of: K2(SiF6):Mn 4+ 、K2(TiF6):Mn 4+ 、K2(SnF6):Mn 4+ 、Cs2(TiF6):Mn 4+ 、Rb2(TiF6):Mn 4+ 、Cs2(SiF6):Mn 4+ 、Rb2(SiF6):Mn 4+ 、Na2(TiF6):Mn 4+ 、Na2(SiF6):Mn 4+ 、Na2(ZrF6):Mn 4+ 、K3(ZrF7):Mn 4 + 、K3(BiF7):Mn 4+ 、K3(YF7):Mn 4+ 、K3(LaF7):Mn 4+ 、K3(GdF7):Mn 4+ 、K3(NbF7):Mn 4+ and K3(TaF7):Mn 4 + .
32. The device of claim 28 or 29, wherein the Mn4+ doped phosphor is K2SiF6:Mn 4+ or Na2SiF6:Mn 4+ .
33. The device of claim 28 or 29, wherein the phosphor composition further comprises at least one other luminescent material.
34. The device of claim 28 or 29, wherein the at least one other luminescent material comprises a quantum dot material.
35. The device of claim 28 or 29, wherein the quantum dot material comprises perovskite quantum dots.
36. The device of claim 28 or 29, wherein the phosphor composition is in the form of a film and is located remote from the LED light source.
37. The device of claim 28 or 29, wherein the phosphor composition is in the form of a film, and the film comprises a multilayer structure, and each layer of the multilayer structure comprises at least one phosphor or quantum dot material.
38. A lighting device comprising the apparatus according to claim 28 or 29.
39. A backlight device comprising the apparatus according to claim 28 or 29.
40. A display device comprising an apparatus according to claim 28 or 29.
41. The device of claim 28 or 29, wherein the LED light source is a mini LED or a micro LED.
42. A television comprising the backlight device according to claim 39.
43. A mobile phone comprising the backlight device according to claim 39.
44. A computer monitor comprising the backlight device according to claim 39.
45. A laptop computer comprising the backlight device according to claim 39.
46. A tablet computer comprising the backlight device according to claim 39.
47. An automotive display comprising the backlight device according to claim 39.
48. The device of claim 41, wherein the device is a self-emissive display.
49. The method of claim 19, wherein the potassium source is KF.
Citation Information
Patent Citations
Processes for preparing color stable red-emitting phosphor particles having small particle size
US11193059B2
Films with narrow band emission phosphor materials
US11254864B2
Phosphor surface treatment method
US20150329770A1
Devices containing a remote phosphor package with red line emitting phosphors and green emitting quantum dots
US20170254943A1
Red emitting phosphor materials for use in LED and LCD applications
US7358542B2